Drought weakens greenhouse gas sink of global wetlands - Longxin Qiao; Xinxin Wang; Hongyang Chen; Jihua Wu; Xiangming Xiao; Ming Nie; Rui-Ting Ju; Yuhan Zheng; Xi Zhang; Qiang He; Xutong Ru; Lijuan Cui; et al. (Environmental Impact Assessment Review, 2027)

SMART-guided discovery of anti-adipogenic guaiane sesquiterpenoids from the roots of Edgeworthia gardneri - Ming-Cui Yang; Lin-Lin Tian; Xiu-Qing Song; Yao-Yue Fan (Phytochemistry, 2026)

A bibliometrics review of non-CO2 greenhouse gas reduction strategies - Yi-Ming Wei; Si-Yu Liu; Li-Jing Liu; Lan-Cui Liu; Qiao-Mei Liang; Xiao-Chen Yuan; Hong-Dian Jiang; Pallav Purohit; Felix Creutzig; Hua Liao; Biying Yu (Energy and Climate Change, 2026)

Experimental measurement and theoretical modeling of liquid density and viscosity for Low-GWP azeotropic refrigerant R516A - Jun Shen; Qilu Huang; Hongsheng Ouyang; Jiao Xu; Ming Xu; Junwei Cui; Chenyang Zhu; Tao Yang (International Journal of Refrigeration, 2026)

Combined exposure to wildfire ash and road salts reshapes skin and gut microbiota and reduces fitness in amphibians - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Yue-liang Pan; Wen-jing Dong; Ming-da Xu; Zhi-wen Luo; Li-yong Cui (Environmental Research, 2026)

Magnetron-sputtered vertically aligned 1 T-rich MoS2 on 3D carbon foam for LiS batteries - Chengxiang Tian; Yao Luo; Ming Jiang; Donghua Wang; Songya Cui; Wensheng Yan (Chemical Engineering Journal, 2026)

Overlooked effects of common alcohol quenching agents on electron transfer pathway in persulfate activation system - Xuerong Zhou; Lin Zhang; Shiyu Liu; Huchuan Yan; Dengsheng Ma; Qihong Yang; Bing Ding; Cui Lai; Ming Yan; Zizhu Peng (Chemical Engineering Journal, 2026)

Greenness across the lifespan and adult respiratory health: A longitudinal cohort study - Yiling Zheng; Yilin Zhang; John S. Ji; Siyi Chen; Yufei Liu; Yuanyuan Yi; Jun Ma; Zhijie Zhang; Ming Wen; Cui Guo (Urban Forestry & Urban Greening, 2026)

Oral self-assembled nanomedicine orchestrates hierarchical regulation of the lipid–ROS–inflammation cascade for comprehensive therapy of non-alcoholic fatty liver disease - Jia-Jian Zhang; Yin-Sheng Tan; Chen-Lei Zhang; Yan Gui; Fan-Zhi Yan; Jie Hou; Xiang-Xuan Liu; Hua Kong; Meng-Ru Guo; Yang-Feng Cui; Xian-He Lin; Tao-Tao Fan; et al. (Chemical Engineering Journal, 2026)

Outdoor thermal comfort differences among orthopedic, oncological and chronic-disease patients in cold-region hospital spaces - Ya Tuo; Songtao Cui; Minghui Sun; Weijie Xia; Songjiang Han; Meng Zhen; Ming Zhang; Kai Nan (Building and Environment, 2026)

A deep learning-based intelligent analysis method for segmental joint under different scenarios - Li Zhang; Huichuan Zhan; Kun Feng; Chen Chen; Xiaoning Cui; Jianming Zhou; Ming Song; Chuan He (Tunnelling and Underground Space Technology, 2026)

Evaluating the collective effects of vertical and ground greening on microclimate and energy consumption in a high-density building array - Dongjin Cui; Ruikun Ge; Xiaolong Zheng; Guozhu Liang; Jian Hang; Cheuk Ming Mak (Sustainable Cities and Society, 2026)

Effect of dissolved organic matter chemical characters on microbial community of paddy soils in subtropical China - Yaxin Liu; Yingcong Ye; Daming Li; Rong Cui; Xiaoli Liu; Ling Chen; Meng Wu; Jia Liu; Xi Guo; Ming Liu (Soil and Tillage Research, 2026)

Influence of enzymatic modification on the structure–function properties of wheat bran arabinoxylan enriched fractions: Interplay of molecular weight and branching degree - Mohsin Rasheed; Boli Guo; Xiangqi Fan; Yingquan Zhang; Bo Zhang; Ming Li; Yutong Cui (Food Bioscience, 2026)

Recovery trajectories of amphibian skin microbiota following ash exposure across translocation and natural recovery scenarios - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Ming-da Xu; Yue-liang Pan; Li-yong Cui (Environmental Pollution, 2026)

Contrasting mineral–microbial pathways drive phosphorus bioavailability under moderate pH shifts in agricultural soils - Meng Qi; Rongyang Cui; Anqiang Chen; Xinmei Zhao; Ming Ni; Zhiwu Li; Hui Yan; Chi Wang; Bin Fu (Applied Soil Ecology, 2026)

Hydrogel-encapsulated microalgae-bacteria consortia for resilient saline agriculture - Xiao-Jing Wang; Nan Wu; Xiao Yu; Si-Ming Li; Zi-Rui Yang; Zhi-Hai Zhong; Kang Wang; Hong-Li Cui; Cheng-Gang Ren; Song Qin (World Journal of Microbiology and Biotechnology, 2026)

Predicting big five personality traits from resting-state EEG connectivity: a connectome predictive modeling study - Chu Zhang; Yao Liu; Yiting Long; Siyuan Hu; Ming Li; Wenkai Bai; Yiting Li; Can Cui; Can Gao (Brain Structure and Function, 2026)

Rapid prediction of wind field in street canyons with infrastructure elements using neural operators - Guozhu Liang; Ruikun Ge; Dongjin Cui; Jian Hang; Gang Hu; Cheuk Ming Mak (Urban Climate, 2026)

Properties of calcareous sand treated by seawater-based biomineralization via bacterial-enzyme induced carbonate precipitation - Ming-Juan Cui; Jian-Bin Wu; Han-Jiang Lai; Jun-Jie Zheng; Zhen Wu; Ye-Wei Zheng; Yan Luo; Wen-Yu Yang (Transportation Geotechnics, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

A heterotrophic nitrification and aerobic denitrification strain capable of antibiotic degradation: From function to mechanism - Jia-Ying Li; You-Wei Cui; Yuan Sui; Ji-Tao Yan; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Ze-You Lu (Environmental Pollution, 2026)

Retrogressive failure mechanisms of ice-rich permafrost slopes under thermal disturbance on the Qinghai–Tibet plateau - Tao Wei; Peng Cui; Ming Peng; Xiaoli Liu; Mingxin Zhao; Jiao Wang; Jiren Xie; Yu Rao (Engineering Geology, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Pre-adaptive resistance to acequinocyl associated with cross-resistance to bifenazate in field populations of Tetranychus urticae across China - Jin-Cui Chen; Hui-Juan Li; Ming Xue; Bo Peng; Jing-Jing Kang; Qi-Yu Chen; Shuai-Yu Wang; Ya-Jun Gong; Shu-Jun Wei (Crop Protection, 2026)

Pear PbrPRKs regulate pollen tube growth via modulation of apical actin and reactive oxygen species homeostasis - Lan Xu; Yuzhen Qian; Yusheng Xu; Haoran Wu; Juan Ma; Jitao Ge; Yuqian Wang; Kaijing Zhang; Yihu Sui; Xueping Zhang; Jingjing Qian; Shuangshuang Jia; et al. (Plant Science, 2026)

Selective catalytic oxidation of ammonia by efficient FeOx in coal ash: insights from experimental and DFT studies - Yili Zhang; Su Zhang; Binxin Fang; Liming Cui; Yixiang Zhang; Wenzhen Zhang; Houzhang Tan; Ming Li; Xuebin Wang (Fuel, 2026)

Maternal inulin intervention ameliorates lipid metabolism disorders in offspring induced by a high-fat diet before or during pregnancy via the gut-liver-adipose axis - Bing Chen; Jia Wu; Xiaole Cui; Yaxing Miao; Lingling Li; Kaixin Su; Changchun Liu; Yane Luo; Ming Du; Wei Song (Food Bioscience, 2026)

An electrolyte incorporating a fluoro−/sulfonate-based functional additive achieves sulfur-rich interphases and stable temperature performance for pouch graphite/LiNi0.8Co0.1Mn0.1O2 batteries - Peiqi Zhou; Xueyi Zeng; Weizhen Fan; Chaojun Fan; Chengyun Wang; Ming Cui; Junmin Nan (Chemical Engineering Journal, 2026)

Gastrodin Ameliorates Blood Pressure by Targeting the PPAR-γ/NF-κB/NLRP3 Signaling Axis in the Hypothalamic Paraventricular Nucleus - Yu Yang; Xiao-Jing Yu; Li-Yan Fu; Jie Qi; Kai-Li Liu; Xiu-Yue Jia; Wei Cui; Qing Su; Ting Huang; Yan-Feng Liang; Hua Tian; Huan Liu; et al. (Cardiovascular Toxicology, 2026)

Harnessing mycelium-based morphology of filamentous fungi in food biomanufacturing: Integrated advances, challenges, and future perspectives - Mengmeng Xu; Song Ming; Jiahao Cui; Yuxi Guo; Liting Zhao; Lei Chen; Guiyang Shi; Daming Fan; Zhongyang Ding (Trends in Food Science & Technology, 2026)

Epimedium polysaccharide alleviates adenine-induced oligoasthenozoospermia in mice by inhibiting ferroptosis and inflammation through TLR4/NF-κB and SLC7A11/GPX4 axis - Kun-Yang Tang; Wang Ai; Xiao-Cui Jiang; Min Xiao; Yan-Yan Zhou; Xiao-Ming Yu; Shu-Hui Chen; Jing-Ling Zhao (Reproductive Biology, 2026)

Provenance and sedimentary processes of the Qiongzhou Strait during the Holocene: Evidence from detrital zircon U-Pb geochronology - Xianlong Zhu; Yao Guan; Heqi Cui; Junmin Jia; Ming Su; Yuxin Qin; Ce Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Integrated material-system optimization of Au-ZnIn2S4-x/carbon substrate composite for boosted photocatalytic hydrogen production from wastewater - Xin Zhang; Wei Zhao; Jing Cui; Xiuchan Zhang; Shaohui Guo; Xian-Ming Zhang (Journal of Environmental Chemical Engineering, 2026)

A Ca-MOF@COF composite and its in situ grown gel membrane for highly efficient capture of Cd2+ - Xue-Mei Liu; Chuang-Chuang Zhang; Kun Yang; Wei-Liang Jin; Guan-Lian Mo; Rui Liu; Hong-Xin Jiang; Hao-Jie Cui; De-Ming Kong (Journal of Cleaner Production, 2026)

Multiscale structural and hydration mechanisms underlying texture improvement of high-amylose rice by broken Zajing rice incorporation - Jiayu Cui; Yiming Wei; Ming Gao; Shiyao Yu; Fei Jia; Xiaowei Zhang; Yapeng Fang (Journal of Cereal Science, 2026)

Multifaceted biocontrol mechanisms of Bacillus amyloliquefaciens F028 against Botrytis cinerea in postharvest tomato fruit - Fu-Lai Han; Jin-Xiu Zhao; Ming-Yi Wang; Meng-Fei Li; Zhe Zhang; Xiao-Hang Cui; Yu-Fei Li; Hao-Jie Jiang; Qing-Xue Jiao; Jie Yang; Xin Liu; Guang-Chao Liu (International Journal of Food Microbiology, 2026)

Prediction of groundwater total nitrogen via an interpretable ensemble machine learning framework: Implications for groundwater diversion management in complex catchments - Qiqi Sun; Yuhuan Cui; Jie Wang; Guanyu Chen; Shuhui Zhang; Ming Yang; Mengyu Liu; Shuang Hao; Lin Liu (Environmental Research, 2026)

Nanoplastics enhance F-53B uptake and synergistically induce colonic inflammation via activation of the B cell receptor pathway - Mengxing Cui; Wenke Yuan; Han Wang; Zhihan Zhang; Huan Gao; Shilin Chen; Xinchao Guan; Yujie He; Xiaoge Yang; Ming Chen; Xiaowen Zeng; Qing Wang (Environmental Pollution, 2026)

Selective depolymerization and upcycling of thermoset polyurethane: From waste foam to easily-degradable flame-retardant film - Kaiming Du; Huiwen He; Zongsheng Liu; Hang Hu; Junguang Zhou; Wenrui Song; Ming Lu; Lingxiao Cui; Meng Ma; Yanqin Shi; Yulu Zhu; Si Chen; et al. (Chemical Engineering Journal, 2026)

New mesoporous UiO-66-OH framework with in-situ grown CsPbBr3 perovskite nanocrystals as a multifunctional sensor for the discrimination and instrument-free detection of three natural food additives - Hou-Qun Yuan; Qian-Wen Yang; Ling-Yi Guo; Yao-Hong Wang; Guan-Qun Li; Qiong-Yue Cui; Zhen-Chong Dou; Zhi-Qiang Cai; Yi-Fan Xia; Guang-Ming Bao (Chemical Engineering Journal, 2026)

Salinity decrease leads to recovery of filamentous bacterial bulking in moderately halophilic aerobic granules: Unraveling the role of fungi - Ze-You Lu; You-Wei Cui; Ya-Nan Mi; Xin-Yu Gu; Rui-Chun Yang; Ming-Xin Su; Jia-Ying Li (Bioresource Technology, 2026)

Transcarotid Artery Revascularization for Asymptomatic Carotid Stenosis: A Systematic Review and Meta-Analysis - Zhi-Cheng Jiang; Qi-Fei Hu; Jia-Ming Huang; Xian-Wei Wang; Tong Lin; Xi-Lin Gao; Jia-Wen Cui; Jing-Lin Zhao; Dong Chen; Shu-Peng Li (Translational Stroke Research, 2026)

MRPL15 as a Key Gene in the Malignant Proliferation of LUAD - ZhuoCai Wang; YunFeng Qian; XuWen Lai; WenZhi Cui; JingXia Luo; WeiPeng Zeng; WenYuan He; Ming Liao (Biochemical Genetics, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Integrated numerical modeling strategies for tree–wind interactions: A review and proposed assessment framework for resilient urban design - Qirui Deng; Dongjin Cui; Lixiao Li; Pengfei Lin; Cheuk Ming Mak (Urban Forestry & Urban Greening, 2026)

Outdoor thermal comfort of elderly people with musculoskeletal pain conditions in summer - Yaqian Deng; Chengxin Li; Weijie Xia; Yichun Cui; Ming Zhang; Kai Nan (Energy and Buildings, 2026)

Balancing the activity–stability trade-off via catalyst–support interface lattice oxygen sharing for acidic OER - Ming Gong; Dongxu Jiao; Qiwen Su; Dewen Wang; Jinchang Fan; Lei Zhang; Xiaoxin Zou; Dantong Zhang; David J. Singh; Yong-Wei Zhang; Zhi Gen Yu; Weitao Zheng; et al. (Chemical Engineering Journal, 2026)

Wetland restoration for waterbird conservation: A framework and its application at Chongming Dongtan in China - Ningning Liu; Yanlin Cui; Sen Yang; Yihao Fang; Yue Ren; Shoudong Zhang; Huan Xu; Xuesong Feng; Wei Wu; Xuena Sun; Dongliang Niu; Ming Nie; et al. (Biological Conservation, 2026)

Quantitative assessment of neutrophil chemotactic migration under coexisting intermediate and terminal chemokine gradients in a microfluidic environment: Applications for immune dysfunction and prognostic evaluation in sepsis - Zhuoyi Zhu; Xiao Yang; Yuhang Yao; Ming Fang; Min Shao; Yutao Zha; Jun Zhao; Junsheng Cui; Xiaoou Ren; Ling Zhu; Xuexue Pu; Qiuling Li; et al. (Analytica Chimica Acta, 2026)

Driving factors on bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants: Evidence from different latitudinal gradients in warm season - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Yuan Sui; Tong Ren; Xin-Yu Gu; Ming-Xin Su; Ze-You Lu (Journal of Water Process Engineering, 2026)

Contrasting responses to environmental stresses for macroinvertebrates and benthic algae in subtropic Qinhuai rivers - Lei Han; Ming Chen; Song Bai; Ang Hu; Peixuan Zhang; Beryl Ochieng; Yifan Cui; Jinfu Liu; Shaojuan Du; Hao Wu; Xiefa Song; Kang Song; et al. (Journal of Hydrology, 2026)

Enhanced performance of Cr-doped CeMn/Hβ catalysts for complete oxidation of chlorobenzene-containing volatile organic compounds and their mechanistic insights - Kang Zhou; Shun Wang; Yunrui Zhao; Wei Zhao; Hui Shi; Zhaoyang Fei; Xian Chen; Jihai Tang; Mifen Cui; Xu Qiao; Ming Xia (Journal of Environmental Chemical Engineering, 2026)

Synergistic effects of enzyme-induced carbonate precipitation (EICP) treatment and geogrid reinforcement on mechanical properties of washed recycled sand - Lian Liang; Ming Huang; Mingjuan Cui; Chaoxian Wang (Geotextiles and Geomembranes, 2026)

Physical Activity and Depressive Mood Share the Structural Connectivity Between Motor and Reward Networks - Shiqi Di; Na Luo; Weiyang Shi; Zhengyi Yang; Jing Sui; Rongtao Jiang; Yue Cui; Zongchang Du; Jiaqi Zhang; Yawei Ma; Haiyan Wang; Congying Chu; et al. (Neuroscience Bulletin, 2026)

Tracing fluid evolution forming multistage wolframite mineralization in vein-type tungsten (-tin) deposit: new insight from LA-ICP-MS analysis of fluid inclusion - Zhi-Lin Cheng; Jun-Yi Pan; Pei Ni; Li-Li Chen; Jian-Ming Cui; Zhe Chi; Jun-Ying Ding (Mineralium Deposita, 2026)

Grazing intensity, microtopography, and soil properties mediate the relationship between soil seed banks and aboveground vegetation in grazed wetlands in a semi-arid region - Mingye Zhang; Shuchen Liu; Shouzheng Tong; Yu An; Ming Jiang; Haitao Wu; Guodong Wang; Dongjie Zhang; Geng Cui (Agriculture, Ecosystems & Environment, 2026)

Associations between cognitive frailty and circulating cardiovascular biomarkers in a memory clinic cohort - Xin Tong Tan; Joyce R. Chong; Eddie J. Y. Chong; Ming Ann Sim; Jiangbo Cui; Siew Pang Chan; Oi Wah Liew; Boon Yeow Tan; Narayanaswamy Venketasubramanian; Arthur Mark Richards; Mitchell K. P. Lai; Christopher Li-Hsian Chen (GeroScience, 2026)

Numerical investigation on hydrodynamic characteristics of floating breakwater with wings using a coupled SPH method - Xin Chen; Ming-yuan Li; Peng-cheng Shi; Hong-lei Lyu; Jie Cui (Marine Georesources & Geotechnology, 2026)

Unveiling the adsorptive/catalytic roles of micro-carbon sphere materials in antibiotic removal: Current status and perspectives - Ning Wang; Wang-mi Chen; Qi Zhou; Yu Dong; Ming-xiao Li; Bei-dou Xi; Jia-qi Hou; Zhen-tao Cui (Water Research, 2026)

Numerical study on natural-ventilated pollutant transportation in street canyons with green infrastructure under vegetation-induced thermal conditions - Dongjin Cui; Tao Zhou; Guozhu Liang; Yue Fan; Cheuk Ming Mak (Urban Climate, 2026)

Can nighttime light proxy comprehensive economic well-being? Evidence from China - Wei Jiang; Jie Liu; Tengfei Long; Ming Liu; Akiyuki Kawasaki; Zhiguo Pang; Denghua Yan; Yizi Shang; Elhadi Adam; Xiaohui Ding; Shiai Cui (Sustainable Cities and Society, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Excess phosphorus increases phosphatase activity and alters phoD-harboring bacterial ecotypes in the pepper rhizosphere - Fansheng Kong; Weihua Su; Chunyan Zhang; Shunli Liu; Prakash Lakshmanan; Yutao Cui; Wei Zhang; Xinping Chen; Ming Lang (Rhizosphere, 2026)

Comprehensive evaluation on potentiality and key bacterial community of heterotrophic nitrification and aerobic denitrification in real wastewater treatment plants - Rui-Chun Yang; You-Wei Cui; Zhen-Ying Li; Ming-Teng Li; Yuan Sui (Process Safety and Environmental Protection, 2026)

Multiscale hydrodynamic optimization and energy valorization in hydrogen-based membrane biofilm reactors: unraveling the lumen-shell interaction - Yanxia Xu; Peifeng Deng; Jinyi Tian; Ming Sun; Yuanyuan Qian; Liming Cui; Jinyang Zhang; Xuejing Yang (Journal of Water Process Engineering, 2026)

Static magnetic field coupled with control of sludge retention time enhancing nitrogen removal via heterotrophic nitrification-aerobic denitrification - Ming-Xin Su; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Xin-Yu Gu; Jia-Ying Li; Ze-You Lu (Journal of Water Process Engineering, 2026)

The influence of fulvic acid on molybdenum bioavailability assessed by Caenorhabditis elegans - Qian Huang; Lingfang Cui; Zhixin Song; Ming Li; Chao Zhang; Wenzhong Tang; Jianyin Huang (Journal of Environmental Management, 2026)

Twinned structure–enhanced S-scheme heterojunction in Zn0.8Cd0.2@g-C3N4 for efficient CO2 photocatalytic reduction - Ming-yang Liu; Hao-wen Zhu; Qing-shan Wang; Cong Liu; Heng-fei Cui; Jun-ying Tang; Rui-tang Guo (Fuel, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Modulation mechanism of starch gelatinization and gluten network restructuring in wheat flour during atmospheric steam treatment - Xiangqi Fan; Jikai Jiang; Mohsin Rasheed; Ming Li; Yingquan Zhang; Yutong Cui; Bo Zhang; Boli Guo (Food Hydrocolloids, 2026)

Determination of nitrogen dilution curves and nitrogen diagnosis for oilseed flax under different nitrogen and plant density - Bin Yan; Zhengjun Cui; Ming Wen; Bing Wu; Haidi Wang; Yifan Wang; Yuhong Gao (European Journal of Agronomy, 2026)

Role of sediment entrainment in the flash-flood to debris-flow transition during cascading landslide dam failures - Jialin Liu; Gordon G.D. Zhou; Yunxu Xie; Kahlil F.E. Cui; Xueqiang Lu; Ming Peng; Wei Zhong; Giulia Bossi (Engineering Geology, 2026)

Sequential drug-releasing electroactive wound dressing accelerates healing of diabetic infected wounds through microenvironmental remodeling - Dapeng Cui; Ziyuan Yang; Yupeng Zhang; Xiaopeng Suo; Ming Cheng; Shuang Fan; Cheng Yang; RuiXia Yu; Tao Wang; Lei Li; Jiaxin Cui; Zhongdi Liu; et al. (Chemical Engineering Journal, 2026)

Cytoplasmic-nuclear remote suppression of c-MYC induces cell cycle arrest and enhances radiotherapy sensitivity in liver cancer via biohybrid platelets - Lin Xiao; Fei Ge; Qinyu Ji; Rui Ji; Yan Wang; Shaoqing Ju; Ming Cui; Donglin Xia; Rongrong Jing (Chemical Engineering Journal, 2026)

Removal of antibiotics and antibiotic resistance genes from swine wastewater by visible-light driven photo bio-electro-Fenton system: Performance, mechanism, and energy self-supply balance - Hanyu Zhang; Ming Li; Yanzhi Cui; Jinqiu Qi; Ruixue Jiang; Banghao Du; Qunqun Liu; Zining Wang; Xiaochen Li (Bioresource Technology, 2026)

Photocatalytic Activation of Persulfate by nZVI/g-C3N4 for Tetracycline Degradation: Performance and Reaction Mechanism - Hanyu Zhang; Yanzhi Cui; Yongzhen He; Jinqiu Qi; Ruixue Jiang; Ming Li; Xiaochen Li (Water, Air, & Soil Pollution, 2026)

Single-nucleus RNA sequencing reveals the underlying roadmap of early gonadal differentiation in teleost - Jialin Wang; Yajuan Huang; Zhongkai Cui; Kaili Zhang; Na Wang; Jun Luo; Yu Song; Bowen Hu; Ming Li; Yadong Chen; Manfred Schartl; Songlin Chen (Science China Life Sciences, 2026)

Establishment of a rapid colorimetric sensor for Microcystin-LR based on specific aptamer and positively charged gold nanoparticles - Xueting Cui; Jun Wang; Tingyu Hou; Ming Cai; Luozhao Wang; Yanna Liu; Jinhua Li (Analytica Chimica Acta, 2026)

Three New Species of Nagrajchalara in Yunnan Province, China - Cui‐Jin‐Yi Li; Qi Zhao; Kevin David Hyde; Feng‐Ming Yu; De‐Qun Zhou; Thilini Chethana Kandawatte Wedaralalage; Prapassorn Damrongkool Eungwanichayapant (New Zealand Journal of Botany, 2026)
During an investigation of Leotiomycetes in a tropical area of Yunnan Province, China, eight saprobic samples were collected from decayed wood and fallen leaves. Based on morphological and phylogenetic evidence from the dataset of partial nuclear 28S rDNA D1‐D2 regions (nLSU) and the nuclear rDNA internal transcribed spacer region ITS1‐5.8S‐ITS2 (ITS), three new species of Nagrajchalara (Pezizellaceae, Helotiales) were identified. Nagrajchalara sinensis and N. stipitata form a sister branch in the phylogeny, but they are phylogenetically distant from N. ailaoensis . Morphologically, N . sinensis is characterized by sessile apothecia, lacking the medullary excipulum, basally branched paraphyses, asci with a J+, hemispherical to subconical apex, 3‐septate ascospores, some of which have brown phialides and hyaline phialoconidia. Nagrajchalara ailaoensis is characterized by sessile apothecia, hyaline to dark brown intricate hyphae of the medullary excipulum, paraphyses filled with brown refractive contents, asci with a J+, rounded to subconical apex, and fusoid‐navicular, 1‐septate ascospores. Nagrajchalara stipitata is characterized by stipitate apothecia, hyaline to reddish‐brown intricate hyphae of the medullary excipulum, unbranched paraphyses, asci with a hemispherical to subconical apex, 3‐septate ascospores, some of which form brown phialides and hyaline phialoconidia. Comprehensive descriptions, illustrations, and phylogenetic analyses support the establishment of all the species described above.

Anatomical connectivity development constrains medial–lateral topography in the dorsal prefrontal cortex - Wen Li; Weiyang Shi; Haiyan Wang; Jin Li; Congying Chu; Yu Zhang; Yue Cui; Luqi Cheng; Kaixin Li; Yuheng Lu; Liang Ma; Ming Song; et al. (Science Bulletin, 2026)

Evidence of heterogeneity in the mantle source of Quaternary Naozhou Island basalts from REEs and Sr-Nd-Pb isotopes - Cui Xiao-Ge; Li Zhi-Hua; Xie Shi-Xiong; Yang Wen-Jian; Wang Ming-Qiu; Cheng Liu-San; Gao Cai-Xia; Jiang Hong-Liang (Lithos, 2026)

Non-contaminative MIL-53(Fe)-anchored ultrafiltration membrane for apple juice sterilization: Anti-biofouling performance and mechanism - Sihang Li; Xun Zhou; Jiahao Cui; Xingjian Zou; Zijian Li; Wirote Youravong; Ming Li; Haihua Wang; Zhenyu Li (Journal of Food Engineering, 2026)

Efficient removal of tetracycline and Cu2+ complexes under neutral pH by photo bio-electro-Fenton system using FeMn-LDH/g-C3N4/MoS2 cathode: Performance and mechanism - Hanyu Zhang; Ming Li; Yanzhi Cui; Jinqiu Qi; Ruixue Jiang; Zining Wang; Xiaochen Li (Journal of Environmental Chemical Engineering, 2026)

Alkalinity change induces succession of heterotrophic and autotrophic nitrifying bacterial communities: Comprehensive insights on the mechanism - Yuan Sui; You-Wei Cui; Rui-Chun Yang; Ya-Nan Mi; Xin-Yu Gu; Jia-Ying Li; Ming-Xin Su (Journal of Environmental Management, 2026)

Evaluation of micro(nano)plastics and additives in human blood: A pilot study with university students - Ming-Hui Huang; Chen-Chou Wu; Wen-Jia Cui; Lei Mai; Eddy Y. Zeng (Environmental Pollution, 2026)

Fatigue behavior and remaining life evaluation of cracked rib-to-deck joints reinforced with inverted U-shaped plates - Ming-zhe Li; Chuang Cui; Qing-hua Zhang; Le-tian Da; Zhen-yu Cheng; Chuan Wei; Feng-kun Cui; Ying-fang Yang (Engineering Structures, 2026)

Engineering the cathode: Key to unlocking the potential of potassium-ion batteries - Yu Dong; Ning Wang; Wang-mi Chen; Qi Zhou; Ming-xiao Li; Zhen-tao Cui; Jia-qi Hou; Wen-lin Ruan; Bei-dou Xi (Chemical Engineering Journal, 2026)

Numerical study of airflow pattern and pollutant dispersion in isolated buildings with various windward re-entry bays - Dongjin Cui; Rongjian Tao; Guozhu Liang; Yiwei Zhang; Cheuk Ming Mak (Building and Environment, 2026)

Advances in natural products with anti-skin photoaging: mechanisms, phytochemical diversity, and therapeutic potential - Yi Luo; Xiao-Cui Liu; Yu-Jie Li; Yu-Jia Wang; Ming-Hua Qiu; Xing-Rong Peng (Phytochemistry Reviews, 2026)

Seismic performance of beam-column joints reinforced with ECC - Long Liu; Hongbo Xiao; Songqiang Wan; Chunling Yan; Yu Wang; Chong Liu; Xiaoze Yang; Liang Cui; Chenjie Hao; Menghao Ming; Boyang Liu; Yingying Bi (Bulletin of Earthquake Engineering, 2026)

Long-term intercropping mitigates warming-induced carbon loss via enhancing microbial and substrate resistance - Wei Wang; Yang Wang; Jian-Ming Li; Meng-Ying Li; Peng He; Yongxing Cui; Sheng-Jun Ji; Wen-Ying Wang; Levis Kavagi; Muhammd Ashraf; Yinglong Chen; Matthias C. Rillig; et al. (Soil Biology and Biochemistry, 2026)

Preparation of iron oxide/montmorillonite catalyst and its green remediation performance of pyrene-contaminated soil - Yun-rui Zhao; Kang Zhou; Xiao-xiao Qi; Hui Shi; Jihai Tang; Mifen Cui; Xu Qiao; Ming Xia (Journal of Water Process Engineering, 2026)

Enhancement role of corncob slow-release carbon source on heterotrophic nitrification and aerobic denitrification process in low C/N wastewater treatment - Xin-Yu Gu; You-Wei Cui; Yuan Sui; Jia-Ying Li; Ming-Xin Su; Ze-You Lu; Rui-Chun Yang (Journal of Environmental Management, 2026)

Chemical characteristics of fine aerosols and associated speciated organic compounds in summer Nanjing, China - Yuanjie Shan; Daoming Li; Shijie Cui; Jiukun Xian; Yunjiang Zhang; Junfeng Wang; Haiwei Li; Ming Wang; Yun Wu; Xinlei Ge (Journal of Environmental Sciences, 2026)

Cationic polyacrylamide (CPAM) assisted leaching of rare earth ore containing clay minerals by inhibiting swelling and promoting permeation of ammonium sulfate solution - Meiling Jiang; Huifang Yang; Wenqian Cui; Yunbo Yang; Zhenyue Zhang; Zhengyan He; Zhigao Xu; Ming Wu; Jun Zhao; Ruan Chi (Hydrometallurgy, 2026)

Recent progress on Cu-based MOF electrocatalysts for CO2 reduction - Heng-fei Cui; Xiao-jing Liu; Cong Liu; Hao-wen Zhu; Ming-yang Liu; Rui-tang Guo (Fuel, 2026)

Low-cost supported ionic liquid [TETA][HCOO]/X-5: Adsorption and regeneration performance for CO2 capture from flue gas - Chengyu Han; Chuanjia Qi; Ying Ming; Jiyun Tang; Yong Dong; Lin Cui (Fuel, 2026)

VOCs-driven ozone extremes during dry and wet heatwaves in the Jiangsu–Shandong–Henan–Anhui Boundary: Integrating meteorological forcings and SHAP interpretation - Chaolong Wang; Sufan Zhang; Yisheng Zhang; Shanshan Cui; Xiaofei Qin; Alex Guenther; Jianhui Bai; Dasa Gu; Jinhua Du; Jingchao Tang; Wanxiang Yao; Ming Wang; et al. (Atmospheric Research, 2026)

Prioritizing root endophytes: maize genotype and nitrogen interaction shape microbial contributions to nitrogen use efficiency - Desheng Hu; Shujie Zhang; Ming Chen; Pengjuan Cui; Ying Jiang; Yanlai Han; Yi Wang (Plant and Soil, 2026)

Cover cropping shifts microbial life-history strategies to promote necromass carbon accumulation through soil metabolite mediation in orchard systems - Yutao Zhang; Jia Liu; Kailou Liu; Daming Li; Rong Cui; Yaxin Liu; Xingjia Xiang; Ming Liu (Soil and Tillage Research, 2025)

Provenance of sediments in the Zhongnan Seamount, South China Sea since MIS 3: Insights from clay minerals and geochemical signatures - Letian Zeng; Ce Wang; Ming Su; Heqi Cui (Quaternary Science Reviews, 2025)

Exploration of superoleophobic multi-bionic microstructures on cemented carbide surface for high-efficiency reduction of workpiece removal energy in turning - Jingxia Guo; Xiaobin Cui; Chuangyang Wang; Dong Wang; Pingmei Ming (Journal of Cleaner Production, 2025)

Photolysis-driven separation of Li/Fe in deep eutectic solvent recycling of spent LiFePO4 batteries: High-efficiency leaching and sustainable regeneration - Ke Cui; Ming-Chun Zhao; Yiran Li; Hao Yu; Xuefan Feng; Fuqin Zhang (Journal of Environmental Chemical Engineering, 2025)

School backpacks and commuter bags: A non-negligible source of human exposure to phthalate monoesters - Wen-Jia Cui; Ming-Hui Huang; Chen-Chou Wu; Lian-Jun Bao; Eddy Y. Zeng (Environmental Pollution, 2025)

An innovative intimately coupled photocatalysis and biodegradation system for simultaneous removal of emerging contaminants and nitrate - Shi-Ming Niu; Thangavel Sangeetha; Xue-Dong Zhang; Wei-Mon Yan; Peng-Fei Li; Jiří Ryšavý; Jakub Čespiva; Min-Hua Cui (Chemical Engineering Journal, 2025)

Controls on sediment composition of riverine drainage system: insights from geochemical proxies in the Pearl River - Heqi Cui; Ce Wang; Liangjie Wei; Letian Zeng; Junmin Jia; Haiteng Zhuo; Ming Su (CATENA, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

A new method using convolutional neural networks to distinguish basalt tectonic settings: breaking through theErnst constraints of incomplete geochemical datasets - Ming Lei; Jian Li; Wenyan Cai; Qingyi Cui; Xuyan Bian; Dezhou Chen; Zhengyang Zhang (Earth Science Informatics, 2025)

Sesamol inhibits fungal growth by destroying the redox dynamic equilibrium in Pestalotiopsis neglecta - Jing-Yu Ji; Li-Ying Huang; Bing Bi; Ya-Jun Wang; Jin-Yan Zhao; Sheng-Yu Zhang; Ze Wang; Shu-ming Cui; Qiao-ya Zhang; Guo-Cai Zhang (Physiological and Molecular Plant Pathology, 2025)

Detection of Escherichia coli O157:H7 in food based on magnetic separation and hybridization chain reaction - Ming Cai; Gaihua Wang; Xueting Cui; Tingyu Hou; Jun Wang; Kun Xu; Jinhua Li (Food Control, 2025)

Individual girder-level evaluation of assembled multigirder bridges using load transverse distribution identified from moving load test data - Hao-Yan Cui; Hai-Tao Sun; Xu Zheng; Ming-Guang Wei; Ting-Hua Yi; Dong-Hui Yang (Engineering Structures, 2025)

Fire resistance of GLB columns under axial and eccentric compression: Experimental and numerical investigation - Yunzhuo Zhu; Zhaoyan Cui; Ming Xu; Liuhui Tu; Dongsheng Huang; Jiajia Ou (Engineering Structures, 2025)

Experiment and theoretical analysis on the rotational behavior of mass glulam bolted and glued-in rod joints - Zheng Su; Ming Xu; Zhaoyan Cui; Ruixiong Li; Hongxin Liu (Engineering Structures, 2025)

A Facile-Synthesized Dual-Network Multi-Ionic Integrated Explosive with Enhanced Detonation Performance and Promoted Aluminum Reactivity - Yun-Fan Yan; Yu Shang; Ming-Yu Guo; Shao-Li Chen; Meng Cui; Zhi-Hong Yu; Wei-Xiong Zhang; Xiao-Ming Chen (Chemical Engineering Journal, 2025)

Antagonistic interactions between hummock formation and microtopography in wetlands modulate soil seed bank dynamics via biotic-abiotic coupling - Mingye Zhang; Shuchen Liu; Shouzheng Tong; Yu An; Ming Jiang; Long Chen; Guodong Wang; Geng Cui; Dongjie Zhang (CATENA, 2025)

CAR19-T/NK cell and circular aptamer–drug conjugate (ApDC) combination treatment increases immunotherapy efficacy - Ling-Qi Kong; Su-Yun Chen; Xu Cui; Ya-Hui Hu; Lian Wang; Jia-Yao Zhu; Lan-Xuan Guan; Bing-Kun Wang; Li-Ting Yang; Kai-Ming Chen; Chao-Ming Zhou (Molecular and Cellular Biochemistry, 2025)

Efficacy of a non-recombinant NADC34-like PRRSV-2 vaccine candidate against a recombinant NADC34-like PRRSV-2 isolate - Ming Qiu; Shuai Li; Meng Cui; Shuai Yang; Xiaoyang Zhu; Yifan Meng; Yanhan Lin; Hong Lin; Zhe Sun; Yuan Wang; Sen Jiang; Wanglong Zheng; et al. (Veterinary Microbiology, 2025)

Bio-optical properties of adjacent cyclonic and anticyclonic eddies in the central and western South China Sea during the summer - Yanfang Xiao; Zhanpeng Zhuang; Ming Xin; Tingwei Cui; Rongjie Liu; Yi Ma; Hanyang Liu; Dingqi Wang; Tengfei Xu; Lei Chen (Progress in Oceanography, 2025)

Two pairs of novel isochromanone derivatives with antiadipogenic effects from the cultures of Ganoderma gibbosum - Yu-Jie Li; Xiao-Cui Liu; Yi Luo; Ming-Hua Qiu; Ping Zhao; Xing-Rong Peng (Phytochemistry Letters, 2025)

Tetraether-based temperature record from Lake Xingyun in southwestern China since late MIS3 and implication for regional differences in temperature reconstruction - Haiyang Yu; Xu Wang; Ming Ji; Shihao Zhang; Gaochao Pan; Licheng Guo; Linlin Cui; Xueyun Ma; Wubiao Li; Dongsheng Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A novel perspective on atrazine-induced stress in potato seedlings and its alleviation by green manure (Vicia villosa): Insights from physiological and underlying mechanisms - Yu Wang; Wansheng Yang; Renyue Ming; Wanqiu Jing; Honghao Cui; Yuping Zhang; Ping Lu (Journal of Hazardous Materials, 2025)

A novel cascade A/O biofilm reactor coupled with an iron autotrophic denitrification biofilter process for treating real municipal wastewater: Deep nutrient removal and ultra-low sludge production - Ming-Teng Li; You-Wei Cui; Ya-Nan Mi; Dong-Xu Zhou; Liu-Xu Jiang (Journal of Environmental Management, 2025)

Overshoot, potential air pollution co-benefits and food shortages - Li-Jing Liu; Qiao-Mei Liang; Felix Creutzig; Hua Tong; Yu-Xuan Xiao; Xiang-Yan Qian; Hao Wang; Si-Yi Wei; Xiao-Chen Yuan; Biying Yu; Lan-Cui Liu; Yi-Ming Wei (Global Environmental Change, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

Synergistic band structure tailoring and texturing enhance cooling-power generation Bifunctionality in Bi0.4Sb1.6Te3 - Lin Liao; Jingjing Cui; Keke Liu; Xili Wen; Xingyan Dong; Ming Liu; Ding Luo; Yu-Ke Zhu; Xianli Su; Jiehe Sui; Jinsong Wu; Xinfeng Tang (Chemical Engineering Journal, 2025)

Multi-mode switching bionic triboelectric-electromagnetic hybrid generator with enhanced broadband power generation performance in river environments - Chenxi Li; Kuankuan Wang; Yixin Liu; Fuhai Zhao; Ming Li; Jianwei Cui; Yutong Wang; Yongming Yao; Tianyu Li (Chemical Engineering Journal, 2025)

Genetic influence of the brain on epigenetic age acceleration: evidence of a large‐scale genetic correlation study - Chengcheng Li; Jiaze Tang; Junshuan Cui; Niya Long; Wu Cen; Qibo Wu; Ming Yang; Liangzhao Chu; Xingwang Zhou (Biogerontology, 2025)

Examining mental resilience of contractor in urban rail transit construction project under disruptive events - Bei-Xuan Dong; Ming Shan; Ji-Hong Cui; Bon-Gang Hwang (Tunnelling and Underground Space Technology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Putting the recent 100-year of Asian summer monsoon weakening into context - Jingyao Zhao; Hai Cheng; Liangkang Pan; Kexin Wang; Jiahui Cui; Ming-Qiang Liang; Xiyu Dong; Jiayu Lu; Qiang Li; Yan Yang (Science Bulletin, 2025)

Oceanic redox variations during the Cambrian Age 2–3 in the Yangtze Block of South China: Evidence from pyrite-based proxies - Fangliang Fu; Caineng Zou; Zhengfu Zhao; Songqi Pan; Wei Wang; Cui Luo; Ganlin Hua; Guanwen Lu; Ming Yuan; Jia Yin; Zhenhua Jing (Marine and Petroleum Geology, 2025)

A literature review of direct air capture technology from a socioeconomic perspective - Yi-Ming Wei; Song Peng; Jia-Ning Kang; Lan-Cui Liu; Yunlong Zhang; Helei Liu; Tong Wu (International Journal of Greenhouse Gas Control, 2025)

Effect of particle size on mechanical properties of bio-cemented sand using enzyme-induced calcite precipitation - Qi-Wu Jiang; Ming Huang; Kai Xu; Ming-Juan Cui; Gui-Xiao Jin; Xiao-Ping Zhang (Geomechanics for Energy and the Environment, 2025)

Integrated multiscale topology optimization of frame structures for minimizing compliance - Kui Liu; Kirk Ming Yeoh; Yehui Cui; Ang Zhao; Yangjun Luo; Zheng Zhong (Engineering Structures, 2025)

Synergistic separation of imprinted composite membranes: Combining a porous graphene oxide skeleton with continuous MOFs nanolayers for superior selective separation - Yilin Wu; Hang Cui; Jiaqing Zhang; Chao Zhou; Rongxin Lin; Zequan Diao; Ming Yan (Desalination, 2025)

Versatile patches constructed using poly (thioctic acid-co-sulfobetaine methacrylate) for personalized drug delivery and health monitoring - Qi Jin; Jiayuan Ding; Yuyang Liu; Huiying Zhang; Zongyao Cui; Ming Wu; Xinxin Hou; Minzhi Duan; Zhigui Su; Yan Zheng; Mei Dong; Xiaoliang Wang (Chemical Engineering Journal, 2025)

Construction and optimization of low carbon-to-nitrogen ratio-adapted Chlorococcum-Bacteria symbiosis for energy-efficient wastewater remediation - Ru Yan; Han Ji; Zhuo-Chao Liu; Mei-Qi Ren; Shuai Wang; Li-Ming Yang; Dan Cui (Bioresource Technology, 2025)

Wheat stripe rust resistance gene Yr9, derived from rye, is a CC-NBS-LRR gene in a highly conserved NLR cluster - Yang Yu; Jiajun Liu; Shengjie Lan; Qihang Chen; Jinlong Li; Haoyuan Song; Chen Pan; Juan Qi; Yu Cui; Xingfeng Li; Ming-Cheng Luo; Fei Ni; et al. (Science China Life Sciences, 2025)

Machine Learning-based Analysis of the 2015 M5.8 Alxa Left Banner Earthquake Sequence - Fan Zhang; Xiao-Ming Han; Dong-Yang Pei; Feng-Zhi Cui; Yi-Hang Bai; Xiao-Zhong Yang (Applied Geophysics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Feldspar dissolution controlled by coal-measure fluids and the impacts on pore structure of tight sandstone reservoirs: The case of the Jurassic Badaowan Formation in the Junggar Basin, Northwestern China - Zhi-Cheng Cui; Ke-Lai Xi; Ying-Chang Cao; Xiang Shan; Wei-Kai Huang; Hua-Jun Guo; Bo Peng; Nian-Ming Zan (Marine and Petroleum Geology, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Geochemistry of sulfides from massive carbonate replacement type tin ore at Gaofeng, Dachang orefield: Insights into precipitation conditions and enrichment of critical metals - Yu-Pei Liu; Pei Ni; Jun-Yi Pan; Wen-Chao Su; Stefano Albanese; Jian-Ming Cui; Yuan-Feng Cai; Ming-Sen Fan; Zhi-Lin Cheng (Journal of Geochemical Exploration, 2025)

Engineering Long-Acting apixaban loaded PLGA microspheres for the treatment of stroke caused by atrial fibrillation - Xue-Ai Liu; Yaseen Hussain; Jiawen Wang; Ping Xia; Xiang-Xiang Huang; Ming-Wei Huo; Ling-Zhi Shi; Jing-Hao Cui; Beom-Jin Lee; Renyu Huang; Yujin Ji; Minggang Wei; et al. (Chemical Engineering Journal, 2025)

Alkalinity role in recovery of disintegrated halophilic aerobic granular sludge treating high salt-alkali wastewater: Insights into community ecology of fungi and bacteria - Ya-Nan Mi; You-Wei Cui; Dong-Xu Zhou; Hui-Juan Yan; Liu-Xu Jiang; Ming-Teng Li (Chemical Engineering Journal, 2025)

Novel galactose-rich polysaccharide from Ganoderma lucidum: structural characterization and immunomodulatory activities - Zhou-Wei Wu; Xiao-Cui Liu; Chen-Xi Quan; Xin-Yu Tao; Yi-Luo; Xue-Fang Zhao; Xing-Rong Peng; Ming-Hua Qiu (Carbohydrate Polymers, 2025)

Seasonal variations in the phenolic compounds and antioxidant activity of Pyrrosia petiolosa (Christ et bar.) Ching - Xiangxiang Cui; Xuan Lu; Chunling Meng; Jianhua Chen; Shaorong Chen; Ruhong Ming; Rongshao Huang; Liangbo Li (Biochemical Systematics and Ecology, 2025)

Olfactory GnRH3 crypt sensory neurons transduce sex pheromone signals to induce male courtship behavior in zebrafish - Xuefan Cui; Lu Chen; Binbin Tao; Xiya Zhang; Yanlong Song; Ji Chen; Ming Duan; Weiwei Li; Kuangxin Chen; Yang Pei; Xuerui Hu; Ke Feng; et al. (Science China Life Sciences, 2025)

Biogeographical patterns of antibiotic resistomes in soil biocrusts from urban green spaces at the continental scale - Yulong Li; Qin Chen; Chao Chang; Mian Zhang; Ming Li; Langjun Cui (Applied Soil Ecology, 2025)

Novel lineages of fungicolous Cordieritidaceae (Helotiales, Leotiomycetes) from southwest China - Feng-Ming Yu; Kandawatte Wedaralalage Thilini Chethana; Cui-Jin-Yi Li; Lei Lei; Jin-Rong Lu; Yi-Yun Guo; Qin-Yun Yang; Vinodhini Thiyagaraja; Qi Zhao (Mycological Progress, 2025)

Molecular identification of heterotrophic nitrification and aerobic denitrification bacteria: From methods development to application demonstration - Rui-chun Yang; You-wei Cui; Zhen-ying Li; Ming-teng Li; Liu-xu Jiang; Ya-nan Mi; Yuan Sui; Hui-kai Liang (Water Research, 2025)

Enhanced retention of arsenite and arsenate through heterogeneous interactions between Fe(III) (Hydr)Oxides and black carbon: a multi-mechanistic study - Bingyu Li; Miaomiao Jing; Jingru Li; Zhuoqing Li; Haojie Cui; Yimin Zhou; Dongning Wei; Saihua Liu; Yunhe Xie; Xionghui Ji; Ming Lei (Chemical Engineering Journal, 2025)

Pilot Exploration of RGMa-BMP4 Signaling in Neutrophil Activation in NMOSD: Integrating Clinical and Molecular Insights - Weihe Zhang; Lei Cui; Yeqiong Zhang; Yang He; Xiaoxuan Li; Yu Wang; Jinsong Jiao; Dantao Peng; Ming Jin; Cheng Xiao (Molecular Neurobiology, 2025)

Stepwise leaching rare earth from weathered crust elution-deposited rare earth ores by the inhibition leaching of aluminum with HMTA - Zhengyan He; Qin Zuo; Yuchen Tang; Wenqian Cui; Zhigao Xu; Ming Wu; Jun Qu; Ruan Chi (Environmental Science and Pollution Research, 2025)

“Turn-on” mode fluorescence detection of amines based on a cationic covalent organic framework linked with C−C single bond - Xue-Nan Feng; Xiao-Yang Liu; Dong-Xiao Cao; Yun-Jie Zhou; Yun-Xi Cui; De-Ming Kong (Journal of Hazardous Materials, 2025)

Au NPs@Co-Ni LDH with a concentration effect for the detection of ancient pigments in wall paintings - Jing Wen; Jiayi Wang; Jiamin Sun; Baichao Zhang; Chao Suo; Jing Cui; Xuchuan Cao; Yaxin Yang; Yuexian Hao; Shaohui Guo; Xiaojian Bai; Xian-Ming Zhang (Journal of Environmental Chemical Engineering, 2025)

Preparation of chitosan/shellac nanoparticles-essential oil Pickering emulsion active film and its application in bread preservation - Jin-Ming Tan; Rui Cui; Teng-Gen Hu; Xiao-Xi Li; Hong Wu (Food Packaging and Shelf Life, 2025)

Nitrogen reduction and split application increased grain yield and agronomic nitrogen use efficiency of oilseed flax (Linum usitatissimum. L) by increasing nitrogen status - Ming Wen; Yuhong Gao; Lizhuo Guo; Bin Yan; Peina Lu; Bin Wu; Yifan Wang; Yue Li; Zhengjun Cui; Peng Xu; Haidi Wang; Yuanyuan Cui; et al. (Field Crops Research, 2025)

An enzyme-activated fluorescent probe for proline aminopeptidase and its applications in anti-infection agent discovery - Ming Zhang; Lei Feng; Shengui He; Chaoyan Han; Yuzhuo Wu; Jingnan Cui; Ping Guo; Dawei Li; Chao Wang; Xiaochi Ma (Chemical Engineering Journal, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Single-well colorimetric sensor array for discrimination and smartphone-assisted detection of catecholamines based on Fe-carbon dots nanozymes - Guang-Ming Bao; Dan-Dan Chen; Yi-Fan Xia; Zhi-Qiang Cai; Shun-Qiang Cui; Xia Wei; Zhen-Chong Dou; Yuan Yuan; Akimana Sandra; Hou-Qun Yuan (Analytica Chimica Acta, 2025)

In vitro efficacy of bovine lactoferrin against bovine viral diarrhea virus - Hongwei Cui; Songda Li; Xiaohuan Yan; Zhaohua Wang; Tianyi Leng; Ming Li; Songli Li (Archives of Microbiology, 2025)

Interspecific differences in nitrogen form acquisition strategies contribute to species dominance - Ming Guan; Xiao‐Cui Pan; Jian‐Kun Sun; Ji‐Xin Chen; Xiao‐Lin Wei; Bernhard Schmid; Michel Loreau; Yu‐Long Feng (Ecology, 2025)
Plant's ability to use prevalent or less prevalent soil nitrogen (N) forms may affect their dominance within vegetation types, and these partitioning‐driven changes in dominance may facilitate species co‐existence. However, the mechanisms underlying these processes remain unclear, particularly given the strong influence of altitude on soil N forms, which in turn affect plant N acquisition strategy. In this study, we first determined the effects of preference and plasticity in N form uptake on partitioning of soil N forms and species dominance, and then assessed the relative importance of these two N form use strategies for 19 dominant and non‐dominant species in three vegetation types along an altitudinal gradient on Changbai Mountain, northeast China. To achieve this, we measured dominance, the contents of different N forms in rhizosphere soils, their proportional contributions to leaf N, and N form uptake preference and plasticity for these 19 species. Our results show significant interspecific differences in the proportional contributions of different soil N forms to leaf N within all three vegetation types, providing a novel mechanism underlying niche differentiation among plants. Species dominance was positively associated with the proportional contributions of soil dissolved organic N (the most prevalent N form) and the main inorganic N form to leaf N, while negatively with that of the subordinate inorganic N. These associations were not altered by the altitude‐driven changes in the absolute and proportional contents of different soil N forms, suggesting a potentially widespread phenomenon. Both preference and plasticity in N form uptake contributed to the proportional contributions of different N forms to leaf N, and therefore to species dominance and co‐existence within vegetation types. Furthermore, N form preference was more critical for non‐dominant relative to dominant species and at high relative to low altitude, while N form uptake plasticity was more important for dominant species and at low altitude. Our study provides robust evidence for the interspecific niche differentiation in N form uptake, contributing to species dominance and co‐existence within vegetation types, and reveals the mechanisms (plasticity and preference) underlying the association between species dominance and the uptakes of different N forms.

Engineering a thermophilic Bacillus thermoamylovorans for degradation of polyethylene terephthalate waste - Yi-Mei Cai; Cui-Can Lu; Tian-Tian Wang; Li-Jun Song; Yu-Ming Deng; Han Xu; Sheng Chen; Wei Xia; Jing Wu; Zheng-Fei Yan (Journal of Cleaner Production, 2025)

Recovery of volatile ethanol gas via microalgal-bacterial consortium: Ethanol-to-acetate conversion pathway boosts lipid production - Liu-Xu Jiang; You-Wei Cui; Ya-Nan Mi; Dong-Xu Zhou; Ming-Teng Li; Rui-Chun Yang (Journal of Environmental Management, 2025)

Impact of agricultural straw open-field burning on concentrations of six criteria air pollutants in China - Hao-Neng Huang; Zhou Yang; Yuming Guo; Jia-Jun Ma; Bo-Wen Ming; Jun Yang; Cui Guo; Li Li; Chun-Quan Ou (Environmental Pollution, 2025)

Multi-objective neural policy approach for agile earth satellite scheduling problem considering image quality - Luona Wei; Yongqiang Cui; Ming Chen; Qian Wan; Lining Xing (Swarm and Evolutionary Computation, 2025)

Optimization of enzymatic hydrolysis of collagen and screening and application of hypolipidemic peptide - Yancheng Bi; Ming Zhang; Ke Liu; Xinran Lv; Xuepeng Li; Xue Gao; Fangchao Cui; Defu Zhang; Jianrong Li (Food Bioscience, 2025)

Clean fuel gas production by multi-step catalytic pyrolysis of antibiotic fermentation residue: Effects of bi-functional catalysts and gas atmosphere on tar removal and desulfurization - Xiaomin Cui; Jiawen Fu; Arun K. Vuppaladadiyam; Suthajini Thiruketheeswaranathan; Weiguo Dong; Ming Zhao (Chemical Engineering Journal, 2025)

CO2 emission from soil inorganic C in coastal croplands of the Yangtze Delta - Jun Cui; Ming Nie; Shuang Wang; Zhenke Zhu; Gongle Shi; Yakov Kuzyakov; Tida Ge (Agriculture, Ecosystems & Environment, 2025)

Correction: Inhibition of 12/15 lipoxygenase by baicalein reduces myocardial ischemia/reperfusion injury via modulation of multiple signaling pathways - Lina Song; Hui Yang; Hong-Xia Wang; Cui Tian; Yu Liu; Xiang-Jun Zeng; Erhe Gao; Yu-Ming Kang; Jie Du; Hui-Hua Li (Apoptosis, 2025)

The impact and mechanisms of YL-IPA08, a potent ligand for the translocator protein (18 kDa) on protection against LPS-induced depression and cognitive dysfunction in rodents - Lin-yu Cui; Jing-yao Duan; Jiao-zhao Yan; Jing-ya Wang; Peng Ren; Li-ming Zhang; Wen-zhi Guo; Wei Dai; Yun-feng Li (Metabolic Brain Disease, 2025)

Effects of extraction and modifications on physicochemical characteristics and bioactivities of lemon (Citrus limon L.) polysaccharides - Wenjing Wu; Ruizhan Chen; Ming Gao; Yan Cai; Helong Bai; Cui Yang; Dongxue Li; Yongtang Wang; Mingze Gong (Food Bioscience, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Synergistic toxicity of cadmium and triadimefon on the microbiota and health of Rana dybowskii tadpoles - Xiao-yun Han; Peng Guo; Qiu-ru Fan; Qing-bo Zhou; Ming-da Xu; Xin-zhou Long; Li-yong Cui; Qing Tong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

A brain-targeted and ROS-responsive natural polysaccharide nanogel for enhancing antidepressant therapy - Dong Xu; Tao Qiao; Yan-Ming Zhou; Xue-Yi Wu; Yuan-Lu Cui (Chemical Engineering Journal, 2025)

Highly accurate deformation adaptive pressure sensor integrated with programmatically fabricated strain localizing yarn - Yiming Ke; Weibing Zhong; Xiaojuan Ming; Kaiyue Cui; Shifan Song; Kangyu Jia; Mufang Li; Yi Xiong; Tao Zhao; Dong Wang (Chemical Engineering Journal, 2025)

Simultaneous nitrogen removal and phosphorus recovery in granular sludge-based partial denitrification/anammox-hydroxyapatite precipitation (PD/A-HAP) process under low C/N ratio and dissolved oxygen limitation - Lijie Chen; Zhenjun Wu; Jiayu Niu; Yihan Wang; Ming Cai; Jiale Xi; Yanlei Cui; Lang Cheng; Xinyi Fan (Bioresource Technology, 2025)

The replication efficacy of NADC34-like porcine reproductive and respiratory syndrome virus 2 is not directly associated with the pathogenicity - Meng Cui; Ming Qiu; Shuai Yang; Yuejia Qiu; Wenhao Qi; Hong Lin; Zhe Sun; Wanglong Zheng; Jianzhong Zhu; Nanhua Chen (Veterinary Microbiology, 2025)

Provenance of sediments in the northern shelf of the South China Sea: Insights from Pb isotopes in detrital K-feldspar - Liangjie Wei; Ce Wang; Heqi Cui; Junmin Jia; Letian Zeng; Ming Su (Marine Geology, 2025)

Spectral fingerprints of DOM-tungsten interactions: Linking molecular binding to conformational changes - Weijun Li; Guobin Liu; Ming Lei; Yaoyu Zhou; Haojie Cui; Huihui Du (Journal of Hazardous Materials, 2025)

Genetic link between concealed granite and tin mineralization in the Yuling tin deposit, Nanling Range, South China: Constraints from zircon and cassiterite U-Pb dating, geochemistry, and Lu-Hf isotopes - Yong-Kang Chen; Pei Ni; Jun-Yi Pan; Yi-Ming Xu; Qi-Zhi Yang; Jian-Ming Cui; Wen-Sheng Li; Guan-Jian Fang (Journal of Geochemical Exploration, 2025)

Precision water recharge facilitates spikelet development and seed growth in Carex schmidtii: Implications for near-natural restoration of degraded semi-arid wetlands - Mingye Zhang; Shuchen Liu; Guodong Wang; Yu An; Ming Jiang; Dongjie Zhang; Geng Cui; Long Yan; Shouzheng Tong (Journal of Environmental Management, 2025)

Ultrathin LDH-coated SnO2 catalysts linked by hydrogen bonding for PMS activation via interlayer high-speed electron transfer channels: Performance and mechanism - Guangjie Lv; Haoyang Ye; Cui Lai; Dengsheng Ma; Xuerong Zhou; Xiuqin Huo; Hao Deng; Lin Tang; Tao Tong; Ming Yan; Shuyuan Hu; Lei Qin (Journal of Environmental Chemical Engineering, 2025)

Dynamic thermal and mass transport in PEM fuel cells at elevated temperatures and pressures: A 3D model study - Qianqian Wang; Jixuan Lu; Weibo Zheng; Bing Li; Jim P. Zheng; Guomin Cui; Liang Hao; Pingwen Ming (Fuel, 2025)

Differential impact of wildfire and rice straw ash on the skin microbiota of Rana dybowskii adults and tadpoles - Xin-zhou Long; Ming-da Xu; Wen-jing Dong; Xiu-mei Yang; Li-yong Cui; Qing Tong (Environmental Pollution, 2025)

Machine learning integrated PMF model reveals influencing factors of ozone pollution in a coal chemical industry city at the Jiangsu-Shandong-Henan-Anhui boundary - Chaolong Wang; Xiaofei Qin; Yisheng Zhang; Dantong Liu; Wenxin Tao; Ming Wang; Sufan Zhang; Jianli Yang; Jinhua Du; Shanshan Cui; Dasa Gu; Yingjie Sun; et al. (Atmospheric Environment, 2025)

Ground motion prediction model for significant duration of horizontal component based on the K-NET database - Qi Zhang; Ruyu Cui; Hao Huang; Ming Zhao; Jingyang Tan (Journal of Seismology, 2025)

Influence of wildfire ash concentration on development, survival, and skin and gut microbiota of Rana dybowskii - Qing Tong; Ming-da Xu; Wen-jing Dong; Xin-zhou Long; Xiao-yun Han; Li-yong Cui (Science of The Total Environment, 2025)

Planar Hall plateau in magnetic Weyl semimetals - Lei Li; Chaoxi Cui; Run-Wu Zhang; Zhi-Ming Yu; Yugui Yao (Science Bulletin, 2025)

A novel framework for fatigue hotspot localization and damage assessment of multi-defect marine structures under random vibration - Dengkai Cui; Ruili Xie; Ming Li; Wei Cheng (Ocean Engineering, 2025)

Novel peptide inhibitor of matrix Metalloproteinases-1 from pufferfish skin collagen hydrolysates and its potential Photoprotective activity via the MAPK/AP-1 signaling pathway - Bei Chen; Shuilin Cai; Lulu Cui; Ting Yu; Kun Qiao; Yongchang Su; Min Xu; Haiyan Tang; Shuji Liu; Ming Yang; Zhiyu Liu (Journal of Photochemistry and Photobiology B: Biology, 2025)

Enhanced removal of sulfonamide antibiotics in water using high-performance S-nZVI/BC derived from rice straw - Xiao-Ming Zou; Tiao Zhang; Yu-Hua Dong; Cui Hu; Li Yin; Yu-Ling Zheng; Mi Li; Xiao-Yu Xiao; Wei Hui (Journal of Environmental Management, 2025)

Association of tungsten with aluminosilicate mineral colloids and silicotungstates in soil porewaters: Insights into the unexpectedly high tungsten mobility in soil - Lei Lu; Jing Sun; Yu Dai; Yaoyu Zhou; Haojie Cui; Ming Lei; Huihui Du (Geochimica et Cosmochimica Acta, 2025)

Lymphatic absorption characteristics of eicosapentaenoic acid -enriched phosphoethanolamine plasmalogen and its gastric and intestinal hydrolysates - Dan-Dan Wang; Xiao-Yu Cui; Xiao-Yue Li; Cheng-Cheng Wang; Chang-Hu Xue; Teruyoshi Yanagita; Tian-Tian Zhang; Yu-Ming Wang (Food Chemistry, 2025)

Screening and characterization of an antifreeze peptide from sea cucumber intestinal protein hydrolysates - Zhe Xu; ShengAo Cao; Na Cui; Rui Zhang; Zijin Qin; Hanxiong Liu; Jianping Wu; Ming Du; Zhijian Tan; Tingting Li (Food Chemistry, 2025)

Inhibiting overgrowth of filamentous fungi by magnetic powders: Combination effects of particle interface toxicity and magnetic microbe - Dong-Xu Zhou; You-Wei Cui; Ya-Nan Mi; Liu-Xu Jiang; Ming-Teng Li; Hui-Kai Liang; Hui-Juan Yan; Xu Wang (Chemical Engineering Journal, 2025)

A “two birds one stone” strategy for self-healing marine coatings with antifouling and anticorrosion properties - Yong-Yin Cui; Tian-Cheng Chen; Jia-Ming Zhai; Ying Liu; Ye-Pin Gu; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2025)

A Comprehensive Assessment of Water Loss and Driving Forces for the Middle Route of the South-to-North Water Diversion Project from Humanistic Perspective - Jinyu Xiao; Quansheng Ge; Ming Hu; Huijuan Cui (Water Resources Management, 2025)

Enhanced CO2 emissions from soil organic matter in agricultural fields during microbial community assemblage - Guozhen Gao; Haiyan Cui; Pengfa Li; Shiyu Ma; Ming Liu; Meng Wu; Zhongpei Li (Biology and Fertility of Soils, 2025)

Combination of plasma acoustic emission signal and laser-induced breakdown spectroscopy for accurate classification of steel - Shilei Xiong; Nan Yang; Haoyu Guan; Guangyuan Shi; Ming Luo; Yoshihiro Deguchi; Minchao Cui (Analytica Chimica Acta, 2025)

Application of botulinum toxin A in tissue repair and regeneration - Xuan-Zhu Guo; Ya-Nan Niu; Xuan Zhou; Qiao Wei; Meng Li; Jia-Ning Xia; Yu-Qi Cui; Chao-Xin Chai; Yi-Ming Wang; Li-Ping Chen (Toxicon, 2024)

The intervention mechanism of Tanshinone IIA in alleviating neuronal injury induced by HMGB1 or TNF-α-mediated microglial activation - Yan-Zhu Quan; Jing-He Wang; Si-Hui Zhang; Guang-Nan Jin; Jing-Mei Lu; Yi-Ming Liu; Hong-Yan Gao; Jin-Yi Zhou; Bing-Zhe Wang; Yan Xin; Yue-Xian Cui; Xiang Xu; et al. (Toxicology in Vitro, 2024)

Effects of vertical greening on the thermal environment and energy consumption in different street canyons - Dongjin Cui; Chang Su; Jian Hang; Mengye Zhu; Guanwen Chen; Cheuk Ming Mak (Sustainable Cities and Society, 2024)

Environmentally relevant level of PFDA exacerbates intestinal inflammation by activating the cGAS/STING/NF-κB signaling pathway - Zhenyan Cui; Xiaoyu Yuan; Yuwei Wang; Zekun Liu; Xiaohong Fei; Kelie Chen; Han-Ming Shen; Yihua Wu; Dajing Xia (Science of The Total Environment, 2024)

Calcium homeostasis imbalance mediates DEHP induced mitochondrial damage in cerebellum and the antagonistic effect of lycopene - Jia-Gen Cui; Hao Zhang; Ming-Shan Chen; Jia-Xin Wang; Yi Zhao; Jin-Long Li (Science of The Total Environment, 2024)

A comprehensive genetic variant reference for the Chinese population - Tao Jiang; Hongzhe Guo; Yadong Liu; Gaoyang Li; Zhe Cui; Xinran Cui; Yue Liu; Yang Li; Anqi Zhang; Shuqi Cao; Tianyi Zhao; Liran Juan; et al. (Science Bulletin, 2024)

Total water level prediction at continental scale: Coastal ocean - Linlin Cui; Fei Ye; Y. Joseph Zhang; Haocheng Yu; Zhengui Wang; Saeed Moghimi; Gregory Seroka; Jack Riley; Shachak Pe'eri; Soroosh Mani; Edward Myers; Kyungmin Park; et al. (Ocean Modelling, 2024)

N-(3-Aminopropyl)-imidazole modified polyamide reverse osmosis membrane for improved permeability and selectivity - Yingying Liu; Wanjing Cui; Xiuge Chen; Ming Wang; Haifeng Zhang; Zhi Wang (Journal of Water Process Engineering, 2024)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

A comprehensive study of catalytic pyrolysis of antibiotic fermentation residue over red mud-Ca(OH)2 composites - Xiaomin Cui; Zhaojia Ting; Jiawen Fu; Suthajini Thiruketheeswaranathan; Weiguo Dong; Ming Zhao (Journal of Hazardous Materials, 2024)

Fluid inclusion LA-ICP-MS constraint on hydrothermal evolution of proximal cassiterite-bearing quartz veins in the giant Gejiu orefield: Implications for controls on metallogenic potential of granite-related skarn system - Zhi-Lin Cheng; Pei Ni; Jun-Yi Pan; Liang Han; Wen-Sheng Li; Stefano Albanese; Zhe Chi; Jun-Ying Ding; Jian-Ming Cui (Journal of Geochemical Exploration, 2024)

Construction mechanisms, synthesis strategies, and photocatalytic applications of homojunction catalysts: A review - Hao-wen Zhu; Rui-tang Guo; Qing-shan Wang; Cong Liu; Heng-fei Cui; Ming-yang Liu; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Effect of pollen consumption on development and intraguild predation of two predatory Coccinellidae - Peng-Liang Xia; Xiu-Fang Wang; Yi Feng; Yong Huang; Fei Ji; Wen-Xiao Cui; Bao-Ming Qiao (Journal of Asia-Pacific Entomology, 2024)

Roles of mTOR-p70S6K signaling pathway and HO-1 in ethylbenzene-induced hepatoxic effects in L02 cells - Siyu Liu; Linlin Chen; Hui Peng; Qiang Zhang; Qiang Zeng; Bo Cui; Ming Zhang (Food and Chemical Toxicology, 2024)

Impact of mutations in carbohydrate binding sites of tandem-repeat type galectin from Takifugu obscurus on its antimicrobial activity - Ying Huang; Li-Fan Cui; Rui Shen; Ding-Yi Chen; Min Jin; Xue Jiao; Yu-Guang Chen; Ming-Xuan Pan; Ya-Dong Hu; Zhe Zhao (Fish & Shellfish Immunology, 2024)

Controls on sediment transport from rivers to trenches in passive and active continental margins - Letian Zeng; Ce Wang; David A. Foster; Ming Su; Heqi Cui; Junmin Jia (Science China Earth Sciences, 2024)

A detailed analysis of 16S rRNA gene sequencing and conventional PCR-based testing for the diagnosis of bacterial pathogens and discovery of novel bacteria - Mei-Na Li; Ting Wang; Nan Wang; Qiang Han; Xue-Ming You; Shuai Zhang; Cui-Cui Zhang; Yong-Qiang Shi; Pei-Zhuang Qiao; Cheng-Lian Man; Teng Feng; Yue-Yue Li; et al. (Antonie van Leeuwenhoek, 2024)

Description and genomic characterization of Cohnella caldifontis sp. nov., isolated from hot springs in Yunnan province, south-west China - Ming-Xian Xiang; Cui-Ping Miao; Dian-Yan Zhang; Juan Wang; Yi-Qing Li; Min Yin; ShuKun Tang (Antonie van Leeuwenhoek, 2024)

Effective law enforcement in gray zone operations: A Chinese perspective of coastguard law implementation in delimited maritime zones - Hong-Ming Cui; Khadija Zulfiqar (Marine Policy, 2024)

Investigating the effects of low-salt processing on the umami peptides of dry-cured ham using peptidomics techniques - Ming Ju; Mingxun Cui; Chunxiang Piao; Baide Mu; Jian Zhang; Lujuan Xing; Changcheng Zhao; Guanhao Li; Wangang Zhang (Food Chemistry, 2024)

Regional detrital zircon record of the drainage sediments surrounding the South China Sea: Provenance signature and tectonic implications - Ce Wang; Heqi Cui; Cheng-Shing Chiang; Ming Su; Letian Zeng; Junmin Jia; Liangjie Wei (Earth-Science Reviews, 2024)

Plasmonic honeycomb-like structures with Bernoulli effect and pre-activation effect for enhanced photocatalytic hydrogen production from waste water - Shaohui Guo; Xuchuan Cao; Jie Su; Jing Cui; Baichao Zhang; Chao Suo; Xiaochuan Duan; Xuanhua Li; Bingqing Wei; Xian-Ming Zhang (Chemical Engineering Journal, 2024)

Vibrational coupling-based multilayer flexible triboelectric nanogenerator for wide-amplitude omnidirectional wave energy harvesting - Tianyu Li; Fuhai Zhao; Kuankuan Wang; Xiao Wang; Chenxi Li; Jianwei Cui; Ming Li; Yongming Yao (Chemical Engineering Journal, 2024)

Simulation-based study of local hydrogen crossover dynamics and their effects on proton exchange membrane fuel cells - Qianqian Wang; Weibo Zheng; Bing Li; Jim P. Zheng; Guomin Cui; Liang Hao; Pingwen Ming (Chemical Engineering Journal, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Synergistic release of Cd(II) and As(V) from ternary sorption systems containing ferrihydrite nanoparticles: The role of binary and ternary surface complexes - Ming Lei; Miaomiao Jing; Dongning Wei; Zhuoqing Li; Yimin Zhou; Boqing Tie; Haojie Cui; Bingyu Li (Chemosphere, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

The influence of Type I and III collagen on the proliferation, migration and differentiation of myoblasts - Duanyang Wang; Feifan Chang; Zhikang Guo; Ming Chen; Taojin Feng; Mingming Zhang; Xiang Cui; Yuheng Jiang; Jia Li; Yi Li; Jinglong Yan (Tissue and Cell, 2024)

Effects of socioeconomic status and regional inequality on the association between PM2.5 and its components and cardiometabolic multimorbidity: A multicenter population-based survey in eastern China - Zhiqian Cui; Xinxu Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Rong Song; Jintao Liu; Rubing Pan; Weizhuo Yi; Xiaoyu Jin; Jian Song; et al. (Science of The Total Environment, 2024)

Unified scheme design and control optimization of flapping wing for next-generation manta ray robot - Qi-meng Liu; Hao Chen; Peng-ming Guo; Guang-sheng Su; Wei-kun Li; Xin-yu Zeng; Di-xia Fan; Wei-cheng Cui (Ocean Engineering, 2024)

Thermally-stable and flame-retardant metal-organic framework-based separator for high-performance lithium-ion batteries - Wen Ren; Jiang Liang; Meng Huang; Wei Qian; Ming Zhao; Fan Qiao; Lianmeng Cui; Zixin Zhang; Junjun Wang; Cheng Zhou; Zhe Wang; Qinyou An; et al. (Chemical Engineering Journal, 2024)

Genetic relationships of Michelia compressa (Magnoliaceae) with Michelia species and its improvement by interspecific hybridization - Luomin Cui; Xiangdong Liu; Jiaqi Liu; Zhiquan Wang; Ziyang Wang; Ying Yang; Chaoguang Yu; Fangyuan Yu; Yunlong Yin; David Creech; Ming Yin; Sijun Zheng (Trees, 2024)

Decoding the fish genome opens a new era in important trait research and molecular breeding in China - Qian Zhou; Jialin Wang; Jiongtang Li; Zhangfan Chen; Na Wang; Ming Li; Lei Wang; Yufeng Si; Sheng Lu; Zhongkai Cui; Xuhui Liu; Songlin Chen (Science China Life Sciences, 2024)

Tracing the magmatic-hydrothermal evolution of the Xianghualing tin-polymetallic skarn deposit, South China: Insights from LA-ICP-MS analysis of fluid inclusions - Yong-Kang Chen; Pei Ni; Jun-Yi Pan; Jian-Ming Cui (Mineralium Deposita, 2024)

A new approach to dividing the tectonic setting of igneous rocks: machine learning and GeoTectAI software - Ming Lei; Wenyan Cai; Xiao Liu; Chao Zhang; Qingyi Cui; Jian Li (Earth Science Informatics, 2024)

Detrital zircons record the provenance and source-to-sink process in the northwestern margin of the South China Sea - Heqi Cui; Ce Wang; Ming Su; Yaping Lei; Letian Zeng; Junmin Jia (Frontiers in Marine Science, 2024)
The northwestern continental margin of the South China Sea, extending from the broad shelf and canyon-growth slope across the Xisha Trough, represents a relic crustal rift that eventually connects to the abyssal plain. However, the provenance and source-to-sink process of sediments in this special topography remains unclear. In this study, we present the detrital zircon U-Pb geochronology of surface sediments from the northwestern margin of the South China Sea to identify the sediment provenance, track the transport pathway, and understand the source-to-sink process in this margin. The results showed that detrital zircons exhibit a wide range of U-Pb ages from 3,062.9 to 41.5 Ma and are characterized by peaks centered on 140–154 Ma, 240–258 Ma, 425–452 Ma, and 738–991 Ma. Statistical analysis indicated that the clastic sediments on the shelf closely resemble those sourced from the Pearl River system. Conversely, sediments on the slope and abyssal plain demonstrated characteristics indicative of multiple sources, primarily originating from the Pearl River, with a minor contribution from the Red River. Further quantitative study revealed a progressive increase (from 8.2% to 43.2%) in the prevalence of Red River-derived sediments with ascending water depth on the shelf and slope, whereas sediment influx in the deepest sector remains predominantly sourced from the Pearl River. This study emphasizes the controls of topography and currents in modulating the transportation of coarse-grained and fine-grained sediments within the source-to-sink system and provides a favorable solution for reconstructing the sedimentary process in continental margins.

In vitro tungsten bioaccessibility in Chinese residential soils: Implications for human health risk assessments and soil screening level derivation - Lei Lu; Ming Lei; Yaoyu Zhou; Haojie Cui; Huihui Du (Journal of Hazardous Materials, 2024)

Improving the thermal-mechanical performance of bio-treated backfill materials by addition of magnetic iron oxide nanoparticles (nano-Fe3O4) - Shuang Li; Ming Huang; Mingjuan Cui; Guixiao Jin; Kai Xu (Geomechanics for Energy and the Environment, 2024)

Rigorous development and comparison of multi-dimensional reactor models encompassing the catalyst domains for steam methane reforming - Chengtian Cui; Dat-Nguyen Vo; Yufei Zhao; Meng Qi; Ming Xia; Doraiswami Ramkrishna; Cornelius Mduduzi Masuku (Chemical Engineering Journal, 2024)

Biotemplate synthesis of graphitic carbon-doped ZnO tube bundles rich in oxygen vacancies for dual-sensing of NO2/H2S at different temperatures - Zhao-Qi Cui; Rui Gao; Guo-Li Chen; Shi-Kai Shen; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Impact and migration behavior of triclosan on waste-activated sludge anaerobic digestion - Min-Hua Cui; Lei Chen; Thangavel Sangeetha; Wei-Mon Yan; Chao Zhang; Xue-Dong Zhang; Shi-Ming Niu; He Liu; Wen-Zong Liu (Bioresource Technology, 2024)

A novel highly dispersed calcium silicate hydrate nanosheets for efficient high-concentration Cu2+ adsorption - Kaibin Cui; Xiaoyu Han; Pengfei Zhou; Ming Hao; Xianku Wang; Liang Bian; Jianan Nie; Guanling Yang; Jinsheng Liang; Xinnan Liu; Fei Wang (Journal of Hazardous Materials, 2024)

Impact of wildfire ash on skin and gut microbiomes and survival of Rana dybowskii - Ming-da Xu; Wen-jing Dong; Xin-zhou Long; Xue-wen Yang; Xiao-yun Han; Li-yong Cui; Qing Tong (Journal of Hazardous Materials, 2024)

Linking Taiwan to the Cathaysia Block during the Cenozoic: Evidence from Pb isotopes in detrital K-feldspar - Ce Wang; Liangjie Wei; Cheng-Shing Chiang; David A. Foster; Heqi Cui; Ming Su (Global and Planetary Change, 2024)

Comparative analysis of physicochemical properties and biological activities of crude polysaccharides isolated from selected Auricularia cornea strains - Asif Ali Khan; Fang-Jie Yao; Feng-Jie Cui; Yu Li; Lixin Lu; Ismail Khan; Abdul Jalal; Ming Fang; Khulood Fahad Alabbosh; Mohamed F. Awad; Noureddine Elboughdiri; Muhammad Wajid Ullah (Food Bioscience, 2024)

Performance evaluation of underground thermal storage integrated dual-source heat pump systems - Liang Shi; Ming Qu; Xiaobing Liu; Tomas Pablo Venegas; Lingshi Wang; Jin Dong; Borui Cui; Haowen Xu; Xiaoli Liu; Yanfei Li (Energy and Buildings, 2024)

Realization of valence band convergence for high thermoelectric performance p-type PbS - Ming Wu; Hong-Hua Cui; Zixuan Chen; Jing Zhou; Hongwei Ming; Zhong-Zhen Luo; Zhigang Zou (Chemical Engineering Journal, 2024)

Non-noble-metal plasmonic parabolic membrane with “pearl necklace” structure for enhanced hydrogen production based on light concentration effect - Shaohui Guo; Baichao Zhang; Xinlei Zhang; Xuchuan Cao; Jing Cui; Chao Suo; Xian-Ming Zhang (Chemical Engineering Journal, 2024)

Quantitative trait locus analysis of gray leaf spot resistance in the maize IBM Syn10 DH population - Lina Cui; Mingfei Sun; Lin Zhang; Hongjie Zhu; Qianqian Kong; Ling Dong; Xianjun Liu; Xing Zeng; Yanjie Sun; Haiyan Zhang; Luyao Duan; Wenyi Li; et al. (Theoretical and Applied Genetics, 2024)

Maize tassel number and tasseling stage monitoring based on near-ground and UAV RGB images by improved YoloV8 - Xun Yu; Dameng Yin; Honggen Xu; Francisco Pinto Espinosa; Urs Schmidhalter; Chenwei Nie; Yi Bai; Sindhuja Sankaran; Bo Ming; Ningbo Cui; Wenbin Wu; Xiuliang Jin (Precision Agriculture, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

The Role of KDM2A and H3K36me2 Demethylation in Modulating MAPK Signaling During Neurodevelopment - Zongyao Ren; Haiyan Tang; Wendiao Zhang; Minghui Guo; Jingjie Cui; Hua Wang; Bin Xie; Jing Yu; Yonghao Chen; Ming Zhang; Cong Han; Tianyao Chu; et al. (Neuroscience Bulletin, 2024)

Replacing soybean meal with fermented rapeseed meal in diets: potential effects on growth performance, antioxidant capacity, and liver and intestinal health of juvenile tilapia (Oreochromis niloticus) - Yaxue Li; Xing Lu; Lixue Dong; Di Peng; Jianmin Zhang; Zongbin Cui; Hua Wen; Juan Tian; Ming Jiang (Fish Physiology and Biochemistry, 2024)

Impact of antibiotic therapy on cutaneous and gut microbiota in Rana dybowskii amphibians: Insights and implications - Xin-zhou Long; Wen-jing Dong; Ming-da Xu; Xue-dong Han; Xiao-yun Han; Li-yong Cui; Qing Tong (Aquaculture, 2024)

Effects of envelope features on building surface temperature and ventilation performance in 2D street canyons - Dongjin Cui; Guozhu Liang; Jian Hang; Zhenyu Yang; Zhengdong Huang; Cheuk Ming Mak (Urban Climate, 2024)

Inorganic flocculant-based soybean urease extraction and its effect on biomineralization - Han-Jiang Lai; Hui Liu; Ming-Juan Cui; Jun-Jie Zheng; Zhi-Bo Chen; Zhi-Chao Zhang (Journal of Cleaner Production, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

Physicochemical properties and cell viability comparison of two Lactiplantibacillus plantarum DNZ-4 microcapsules and its application in beverages - Cui-Cui Sun; Ming Yi; Yu Miao; Yan Song; Guo-Fang Zhang; Peng Du; Ai-Li Li; Li-Bo Liu; Chun Li (Food Hydrocolloids, 2024)

Newly graphene/polypyrrole (rGO/PPy) modified carbon felt as bio-cathode in bio-electrochemical systems (BESs) achieving complete denitrification - Yue-Jia Yang; Shuai Wang; Da Kang; Xin Lu; Zi-Chang Lu; Zhuo-Chao Liu; Li-Ming Yang; Dan Cui (Environmental Research, 2024)

H*ads dynamics engineering via bimetallic Pd–Cu@MXene catalyst for enhanced electrocatalytic hydrodechlorination - Lan-Ying Liu; Min-Hua Cui; John Justo Ambuchi; Shi-Ming Niu; Xin-Hui Li; Wo-Long Wang; He Liu; Guo-Shuai Liu; Ai-Jie Wang (Environmental Research, 2024)

Versatile MOF-based nanofibrous heterostructures for engineering the CO2 photoreduction activity and selectivity: From CO to C2H5OH - Xu-Chao Xia; Feng Cheng; Peng Sun; Amare Aregahegn Dubale; Hao Han; En-Tian Cui; Jun Song; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Dynamic Changes of the Infralimbic Cortex and Its Regulation of the Prelimbic Cortex in Rats with Chronic Inflammatory Pain - Longyu Ma; Lupeng Yue; Shuting Liu; Yu Zhang; Meng Zhang; Shuang Cui; Feng-Yu Liu; Ming Yi; You Wan (Neuroscience Bulletin, 2024)
The prelimbic cortex (PL) is actively engaged in pain modulation. The infralimbic cortex (IL) has been reported to regulate the PL. However, how this regulation affects pain remains unclear. In the present study, we recorded temporary hyper-activity of PL pyramidal neurons responding to nociceptive stimuli, but a temporary hypo-function of the IL by in vivo electrophysiological recording in rats with peripheral inflammation. Manipulation of the PL or IL had opposite effects on thermal hyperalgesia. Furthermore, the functional connectivity and chemogenetic regulation between the subregions indicated an inhibitory influence of the IL on the PL. Activation of the pathway from the IL to the PL alleviated thermal hyperalgesia, whereas its inhibition exacerbated chronic pain. Overall, our results suggest a new mechanism underlying the role of the medial prefrontal cortex in chronic pain: hypo-function of the IL leads to hyperactivity of the PL, which regulates thermal hyperalgesia, and thus contributes to the chronicity of pain.

Toxic effect and mRNA mechanism of moon dust simulant induced pulmonary inflammation in rats - Jintao Wang; Yuan Xue; Bin Wu; Ming Lei; Honglei Ma; Xinxing He; Qi Tan; Jian Guan; Wei Song; Renfu Li; Xinguang Cui (Toxicology, 2024)

Metabolites assay offers potential solution to improve the rooster semen cryopreservation - Xue Du; Yuanning Zhang; Duoxi Li; Jie Han; Yali Liu; Lijuan Bai; Tao Huang; Ming Cui; Panlin Wang; Xianzhong Zheng; Ayong Zhao (Theriogenology, 2024)

Variations in plant root traits shaped by intraspecific interactions are species-specific - Shu Guo; Ka Ming Li; Min Liu; Weining Wang; Changhua Fan; Xingliang Xu; Xiaoyong Cui (Rhizosphere, 2024)

Numerical simulation of wedges slamming non-Newtonian fluids based on SPH method - Jie Cui; Qing Yao; Xin Chen; Ming-Yuan Li; De-Tao Xu (Ocean Engineering, 2024)

Re-watering solution facilitates seed germination and seedling growth of Carex schmidtii: Implication for species re-introduction in degraded semi-arid wetlands - Mingye Zhang; Shuchen Liu; Yu An; Dongjie Zhang; Qing Qi; Ming Jiang; Geng Cui; Shouzheng Tong (Journal of Environmental Management, 2024)

Grappling with the trade-offs of carbon emission trading and green certificate: Achieving carbon neutrality in China - Haoran Wang; Tiantian Feng; Jiajie Kong; Mingli Cui; Ming Xu (Journal of Environmental Management, 2024)

Efficient detection of geosmin and 2-methylisoborneol in natural/drinking water by UIO66-NH2 composite-derived porous carbon - Wei Liu; Ming Yang; Shuang Wang; Yan-Sai Bao; Yong-He Cui; Ling-Xu Meng; Liang-Cheng Li; Yang Wu; Yu-Yang Zhang (Journal of Environmental Chemical Engineering, 2024)

Significance of non-DLVO interactions on the co-transport of levofloxacin and titanium dioxide nanoparticles in porous media - Yiqun Cui; Ming Wu; Guoping Lu; Zhou Cheng; Meng Chen; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Environmental Pollution, 2024)

Hydrological and biogeochemical processes controlling riparian groundwater quantity and quality during riverbank filtration - Geng Cui; Xiaosi Su; Shida Zheng; Shouzheng Tong; Ming Jiang (Environmental Pollution, 2024)

Effects of Melatonin Priming on the seed Germination, Seedling Growth, and Biochemical Characteristics of Suaeda Corniculata Exposed to Salinity and Osmotic Stresses - Mingye Zhang; Ming Jiang; Dongjie Zhang; Shuchen Liu; Qing Qi; Yuan Xin; Yu An; Geng Cui; Xianguo Lyu; Shouzheng Tong (Journal of Soil Science and Plant Nutrition, 2024)

Antiproliferative polycyclic polyprenylated acylphloroglucinols from Garcinia paucinervis - Cui-Cui Jia; Jing-Jing Xue; Zhan-Lin Li; Da-Hong Li; Hui-Ming Hua (Natural Product Research, 2024)

Effect of glazing on the indoor environment in a lift-up canteen - Dongjin Cui; Yuning Lou; Yaxing Du; Lei Yuan; Cheuk Ming Mak (Urban Climate, 2024)

Rice straw ash and amphibian health: A deep dive into microbiota changes and potential ecological consequences - Wen-jing Dong; Ming-da Xu; Xue-wen Yang; Xiu-mei Yang; Xin-zhou Long; Xiao-yun Han; Li-yong Cui; Qing Tong (Science of The Total Environment, 2024)

Green preparation of CaO-based CO2 adsorbent by calcium-induced hydrogenation of shell wastes at room/moderate temperature - Yang-Yang Hao; Ming-Xiu Xiao; Guo-Cui Mao; Jin-Peng Wang; Zhan-Kuo Guo; Bao-Xia Dong; Yun-Lei Teng (Journal of Environmental Management, 2024)

Elemental and Sr isotopic compositions of plagioclase as an indicator of lunar source-rock type: Insights from Chang'e 5 plagioclase fragments - Le Zhang; Ya-Nan Yang; Zhi-Ming Chen; Jintuan Wang; Cheng-Yuan Wang; Ze-Xian Cui; Yan-Qiang Zhang; Yi-Gang Xu (Icarus, 2024)

Overall quality changes and deterioration mechanism of fragrant rapeseed oils during 6-Month storage - Chen Chen; Ping-Ping Ye; Feng-Jie Cui; Ming Tan; Hai-Bo Zhang; Tong-Lin Zhou; Jian-Cheng Shi; Xue-Quan Shu; Zhi-Wei Chen (Food Chemistry, 2024)

Effects of hydrological regimes on soil seed banks in the Carex hummock in wetlands: Implications for restoration - Mingye Zhang; Shuchen Liu; Dongjie Zhang; Qing Qi; Yu An; Geng Cui; Yue Gao; Ming Jiang; Xianguo Lyu; Shouzheng Tong (Ecological Engineering, 2024)

Waste cigarette butts-templated synthesis of in-situ graphitic carbon-doped ZnO fibers boosting dual-selectivity NO2/butanone at different temperatures - Zhao-Qi Cui; Ze Wei; Cong Chen; Yuan-Yuan Sun; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Correction to: Efects of Manganese and Iron, Alone or in Combination, on Apoptosis in BV2 Cells - Yuan-yuan Fang; Cui-liu Gan; Jian-chao Peng; Yu-han Xie; Han-xiao Song; Ya-qi Mo; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2024)

Effects of Manganese and Iron, Alone or in Combination, on Apoptosis in BV2 Cells - Yuan-yuan Fang; Cui-liu Gan; Jian-chao Peng; Yu-han Xie; Han-xiao Song; Ya-qi Mo; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2024)

Using the paddy eco-ditch wetland system to reduce nitrogen non-point source pollution discharge from paddies: A consecutive six-year study in the Yunnan Plateau, China - Huanhao Han; Xinru Wang; Haili Zheng; Bo Liu; Rong Gao; Yuanlai Cui; Xiaogang Liu; Shixiang Gu; Bochao Zhang; Ming Yang (Agriculture, Ecosystems & Environment, 2024)

Microbial life‐history strategies mediate microbial carbon pump efficacy in response to N management depending on stoichiometry of microbial demand - Liyang Yang; Alberto Canarini; Wushuai Zhang; Ming Lang; Yuanxue Chen; Zhenling Cui; Yakov Kuzyakov; Andreas Richter; Xinping Chen; Fusuo Zhang; Jing Tian (Global Change Biology, 2024)
The soil microbial carbon pump (MCP) is increasingly acknowledged as being directly linked to soil organic carbon (SOC) accumulation and stability. Given the close coupling of carbon (C) and nitrogen (N) cycles and the constraints imposed by their stoichiometry on microbial growth, N addition might affect microbial growth strategies with potential consequences for necromass formation and carbon stability. However, this topic remains largely unexplored. Based on two multi‐level N fertilizer experiments over 10 years in two soils with contrasting soil fertility located in the North (Cambisol, carbon‐poor) and Southwest (Luvisol, carbon‐rich), we hypothesized that different resource demands of microorganism elicit a trade‐off in microbial growth potential (Y‐strategy) and resource‐acquisition (A‐strategy) in response to N addition, and consequently on necromass formation and soil carbon stability. We combined measurements of necromass metrics (MCP efficacy) and soil carbon stability (chemical composition and mineral associated organic carbon) with potential changes in microbial life history strategies (assessed via soil metagenomes and enzymatic activity analyses). The contribution of microbial necromass to SOC decreased with N addition in the Cambisol, but increased in the Luvisol. Soil microbial life strategies displayed two distinct responses in two soils after N amendment: shift toward A‐strategy (Cambisol) or Y‐strategy (Luvisol). These divergent responses are owing to the stoichiometric imbalance between microbial demands and resource availability for C and N, which presented very distinct patterns in the two soils. The partial correlation analysis further confirmed that high N addition aggravated stoichiometric carbon demand, shifting the microbial community strategy toward resource‐acquisition which reduced carbon stability in Cambisol. In contrast, the microbial Y‐strategy had the positive direct effect on MCP efficacy in Luvisol, which greatly enhanced carbon stability. Such findings provide mechanistic insights into the stoichiometric regulation of MCP efficacy, and how this is mediated by site‐specific trade‐offs in microbial life strategies, which contribute to improving our comprehension of soil microbial C sequestration and potential optimization of agricultural N management.

A new diterpenoid from the leaves and twigs of Croton lachnocarpus Benth - Xiao-Qing Zhan; Qian Wu; Mei-Jie Wang; Li Liu; Wen-Bo Cui; Feng-Li An; Feng-Ming Qi; Dong-Qing Fei; Zhan-Xin Zhang (Natural Product Research, 2024)

Experimental investigation of biaxial compressive mechanical property of NPR anchored rock with different preload forces - Xiaoming Sun; Lei Wang; Li Cui; Yong Zhang; Ming Jiang (Tunnelling and Underground Space Technology, 2024)

Fluid inclusion constraint on sulfide precipitation in wolframite-quartz veins: A case study of the giant Dajishan W polymetallic deposit, South China - Jian-Ming Cui; Pei Ni; Jun-Yi Pan; Wen-Sheng Li (Journal of Geochemical Exploration, 2024)

Kinematic response analysis of a three-dimensional lifeboat water entry based on smoothed particle hydrodynamics - Ming-Yuan Li; Jie Cui; Xin Chen; Chang-Jun Gu; Bright Masvaya (Ocean Engineering, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

A two-step Bayesian network-based process sensitivity analysis for complex nitrogen reactive transport modeling - Heng Dai; Jiali Ju; Dongwei Gui; Yan Zhu; Ming Ye; Yujiao liu; Jiebo Cui; Bill X. Hu (Journal of Hydrology, 2024)

A ground-independent method for obtaining complete time series of in situ evapotranspiration observations - Wangyipu Li; Zhaoyuan Yao; Xiaoduo Pan; Zhihao Wei; Bo Jiang; Jing Wang; Ming Xu; Yaokui Cui (Journal of Hydrology, 2024)

A ratiometric fluorescent indicator-displacement assay for on-site determination and intracellular imaging of nitroxinil - Cui-Zhen Lu; Cai-Yun Wang; Chao Song; Tianyi Qin; Taoyuze Lv; Conghui Zeng; Shihong Chen; Zhongyong Xu; Zhiqing Xun; Bin Liu; Ya-Long Wang; Ming-Qiang Zhu (Food Chemistry, 2024)

Green space and its types can attenuate the associations of PM2.5 and its components with prediabetes and diabetes—— a multicenter cross-sectional study from eastern China - Zhiqian Cui; Rubing Pan; Jintao Liu; Weizhuo Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Li Liu; Ning Wei; Rong Song; Jiajun Yuan; et al. (Environmental Research, 2024)

Dual-model biomanufacturing of porous biomimetic scaffolds with concentrated growth factors and embedded endothelial vascular channels for bone defect regeneration - Zhi Cui; Luping Zhou; Junjie Huang; Liang Xu; Zhiyu Ding; Hai Hu; Xu Cao; Ming Zhao; Song Wu (Chemical Engineering Journal, 2024)

Thermally managed and fireproof composite aerogels for safer and year-round energy saving - Wei Cai; Zhaoxin Li; Heng Xie; Wei Wang; Tianyang Cui; Bicheng Lin; Liangyuan Qi; Xin Hu; Yu Du; Yang Ming; Shuo Shi; Daming Chen; et al. (Chemical Engineering Journal, 2024)

Effects of envelope features on pollutant exposure in 2D street canyons - Dongjin Cui; Guozhu Liang; Jian Hang; Xingdi Li; Cheuk Ming Mak (Building and Environment, 2024)

OsGEX3 affects anther development and improves osmotic stress tolerance in rice - Han Bao; Yuchao Cui; Li Ge; Yan Li; Xiaorong Xu; Ming Tang; Yin Yi; Liang Chen (Planta, 2024)

Evaluating rare-earth constraints on wind power development under China's carbon-neutral target - Ziming Hu; Biying Yu; Lan-Cui Liu; Yi-Ming Wei (Science of The Total Environment, 2024)

Improved solar-driven water purification using an eco-friendly and cost-effective aerogel-based interfacial evaporator with exceptional photocatalytic capabilities - Cui Du; Kun Fang; Huanying Zhang; Jing Xu; Ming-An Sun; Shengyang Yang (Journal of Environmental Management, 2024)

Research on fault diagnosis strategy of air-conditioning system based on signal demodulation and BPNN-PCA - Qizheng Ma; Caiping Yue; Ming Yu; Yongxing Song; Ping Cui; Yueping Yu (International Journal of Refrigeration, 2024)

Two-phase modelling of erosion and deposition process during overtopping failure of landslide dams using GPU-accelerated ED-SPH - Mingjun Zhou; Zhenming Shi; Chong Peng; Ming Peng; Kahlil Fredrick E. Cui; Bo Li; Limin Zhang; Gordon G.D. Zhou (Computers and Geotechnics, 2024)

Insight into hydrogen production through halotolerant and cellulose-degrading Clostridium thermopalmium - Sheng-Jie Chen; Ming-Jun Zhu; Si-Ying Cui (Chemical Engineering Journal, 2024)

Regulation of Hepatocellular Cholesterol Metabolism By Lactobacillus Paracasei BY2 and Its Embedding Delivery - Hua-Ling Cui; Meng-Fan Li; Sheng-Ya Liu; Ming Yu; Wen-Yong Lou (Probiotics and Antimicrobial Proteins, 2024)

OsNAC103, an NAC transcription factor negatively regulates plant height in rice - Yan Li; Liming Zhao; Chiming Guo; Ming Tang; Wenli Lian; Siyu Chen; Yuehan Pan; Xiaorong Xu; Chengke Luo; Yin Yi; Yuchao Cui; Liang Chen (Planta, 2024)
Main conclusion OsNAC103 negatively regulates rice plant height by influencing the cell cycle and crosstalk of phytohormones. Abstract Plant height is an important characteristic of rice farming and is directly related to agricultural yield. Although there has been great progress in research on plant growth regulation, numerous genes remain to be elucidated. NAC transcription factors are widespread in plants and have a vital function in plant growth. Here, we observed that the overexpression of OsNAC103 resulted in a dwarf phenotype, whereas RNA interference (RNAi) plants and osnac103 mutants showed no significant difference. Further investigation revealed that the cell length did not change, indicating that the dwarfing of plants was caused by a decrease in cell number due to cell cycle arrest. The content of the bioactive cytokinin N 6 -Δ 2 -isopentenyladenine (iP) decreased as a result of the cytokinin synthesis gene being downregulated and the enhanced degradation of cytokinin oxidase. OsNAC103 overexpression also inhibited cell cycle progression and regulated the activity of the cell cyclin OsCYCP2;1 to arrest the cell cycle. We propose that OsNAC103 may further influence rice development and gibberellin–cytokinin crosstalk by regulating the Oryza sativa homeobox 71 ( OSH71 ). Collectively, these results offer novel perspectives on the role of OsNAC103 in controlling plant architecture.

Ventral Hippocampal CA1 Pyramidal Neurons Encode Nociceptive Information - Yue Wang; Naizheng Liu; Longyu Ma; Lupeng Yue; Shuang Cui; Feng-Yu Liu; Ming Yi; You Wan (Neuroscience Bulletin, 2024)
As a main structure of the limbic system, the hippocampus plays a critical role in pain perception and chronicity. The ventral hippocampal CA1 (vCA1) is closely associated with negative emotions such as anxiety, stress, and fear, yet how vCA1 neurons encode nociceptive information remains unclear. Using in vivo electrophysiological recording, we characterized vCA1 pyramidal neuron subpopulations that exhibited inhibitory or excitatory responses to plantar stimuli and were implicated in encoding stimuli modalities in naïve rats. Functional heterogeneity of the vCA1 pyramidal neurons was further identified in neuropathic pain conditions: the proportion and magnitude of the inhibitory response neurons paralleled mechanical allodynia and contributed to the confounded encoding of innocuous and noxious stimuli, whereas the excitatory response neurons were still instrumental in the discrimination of stimulus properties. Increased theta power and theta-spike coupling in vCA1 correlated with nociceptive behaviors. Optogenetic inhibition of vCA1 pyramidal neurons induced mechanical allodynia in naïve rats, whereas chemogenetic reversal of the overall suppressed vCA1 activity had analgesic effects in rats with neuropathic pain. These results provide direct evidence for the representations of nociceptive information in vCA1.

Ionospheric response and the impact on GPS positioning accuracy during the Tonga volcano eruption on 15 January 2022 - Fuyang Ke; Wanganyin Cui; Lulu Ming; Xiangxiang Hu (Advances in Space Research, 2024)

Two new anthraquinone derivatives from Saprosma crassipes H. S. Lo - Xin-Shu Ji; De-Cai Dai; Yi-Tong Wang; Jing-Yi Cui; Hai-Xiang Li; Xin-Ming Song; Ji-Ling Yi; Xue-Ming Zhou (Natural Product Research, 2024)

Thin film composite polyamide nanofiltration membranes with interlayer constructed with core-shell structured polystyrene-polyacrylamide nanospheres for antibiotics separation - Ben-Qing Huang; Hong-Guang Cui; Tian-Yun Feng; Cai-Ling Yuan; Ai-Lian Chang; Ming-Lu Shao; Chi-Fan Zhu (Journal of Water Process Engineering, 2024)

Numerical analysis of micro lunar dust deposition in the human nasal airway - Xinguang Cui; Wei Song; Yuan Xue; Hao Jing; Ming Lei; Honglei Ma; Xinxing He; Pengfei Zou; Bin Wu; Jintao Wang (Journal of Hazardous Materials, 2024)

Effects of wild boar grubbing on the soil nematode community subject to seasonal variation in a broad-leaved Korean pine forest in Northeast China - Zhong Jie Sun; Heikki Setälä; Ya Xuan Cui; Chen Meng; Ming Ming Cui; Feirong Ren; Shi Jie Han; Jun Qiang Zheng (Forest Ecology and Management, 2024)

Application of a novel zirconium coagulant in the coagulation-ultrafiltration process: Fluoride removal and membrane fouling alleviation - Le Qu; Yonghai Gan; Bin Xu; Bingdang Wu; Wei Wu; Tianyin Huang; Ming Kong; Jianying Chao; Chengcheng Ding; Yibin Cui (Chemical Engineering Journal, 2023)

Centennial-scale monsoon collapses during Marine Isotope Stage (MIS)7e detected in a northern Chinese stalagmite record - Wuhui Duan; Ming Tan; Lisheng Wang; Xuefeng Wang; Zhibang Ma; Linlin Cui; Zhengyi Xiao (Science China Earth Sciences, 2023)

Genome-wide identification and expression analysis of U-box gene family in Juglans regia L. - Hanif Khan; Umar Zeb; Sadaf Gul; Azizullah Aziziullah; Naushad Ali; Sajid Fiaz; Asmaa M. Abushady; Shariat Ullah; Salar Muhammad; Kotb A. Attia; Itoh Kimiko; Fengjie Cui; et al. (Genetic Resources and Crop Evolution, 2023)

Population genetics informs new insights into the phytogeographic history of Juglans regia L. - Hanif Khan; Irfan Ullah; Keith Woeste; Sajid Fiaz; Umar Zeb; Abdelhalim I. Ghazy; Azizullah Azizullah; Salma Shad; Maria E. Malvolti; Ming Yue; Kotb A. Attia; Arif A. Mohammed; et al. (Genetic Resources and Crop Evolution, 2023)

The 10 Most Influential Heavy Rain Events in China in 2022: Selection and Evaluation - Ao Li; Hao Yang; Chunguang Cui; Tao Peng; Yishan Liao; Ming Xu; Xiaofang Wang (Journal of Meteorological Research, 2023)

Study on combustion stability and flame development of ammonia/n-heptane dual fuel using multiple optical diagnostics and chemical kinetic analyses - Mingsheng Wen; Haifeng Liu; Yanqing Cui; Zhenyang Ming; Lei Feng; Guanyue Wang; Mingfa Yao (Journal of Cleaner Production, 2023)

Selective hydrogenation of eggshell/clamshell to methane with the assistance of the alkaline earth and transition metals at room temperature - Ming-Xiu Xiao; Guo-Cui Mao; Jin-Peng Wang; Zhan-Kuo Guo; Bao-Xia Dong; Yun-Lei Teng (Fuel, 2023)

Insight into the selection of oxidant in persulfate activation system: The effect of the target pollutant properties - Xuerong Zhou; Eydhah Almatrafi; Shiyu Liu; Huchuan Yan; Dengsheng Ma; Shixian Qian; Lei Qin; Huan Yi; Yukui Fu; Ling Li; Mingming Zhang; Fuhang Xu; et al. (Journal of Hazardous Materials, 2023)

Atomic hydrogen-mediated enhanced electrocatalytic hydrodehalogenation on Pd@MXene electrodes - Lan-Ying Liu; Guo-Shuai Liu; Shi-Ming Niu; He Liu; Min-Hua Cui; Ai-Jie Wang (Journal of Hazardous Materials, 2023)

Integrated MOVES model and machine learning method for prediction of CO2 and NO from light-duty gasoline vehicle - Run Liu; Hong-di He; Zhe Zhang; Cui-lin Wu; Jin-ming Yang; Xing-hang Zhu; Zhong-ren Peng (Journal of Cleaner Production, 2023)

Experimental study on Diels-Alder addition of conjugated dienes directly from cracking C5 fraction by continuous micro-channel reactors - Zehao Jing; Tingting Ge; Hui Guo; Yuchao Li; Zhou Li; Cuncun Zuo; Ming Wang; Haofei Huang; Lin Guo; Guangjun Cui (Fuel, 2023)

Insight into the selective oxidation behavior of organic pollutants via Ni-N4-C mediated electron transfer pathway - Huchuan Yan; Cui Lai; Shiyu Liu; Dongbo Wang; Xuerong Zhou; Mingming Zhang; Ling Li; Dengsheng Ma; Fuhang Xu; Xiuqin Huo; Lin Tang; Ming Yan; et al. (Chemical Engineering Journal, 2023)

Rotenone nanoparticles based on mesoporous silica to improve the stability, translocation and insecticidal activity of rotenone - Wangjin Xu; Dianjing Shen; Xiaojun Chen; Ming Zhao; Tianle Fan; Qinchao Wu; Zhiyuan Meng; Jiajia Cui (Environmental Science and Pollution Research, 2023)

The role of BECCS technology in achieving carbon neutrality: evidences from China’ coal power sector - Yun-Long Zhang; Jia-Ning Kang; Min Dai; Juan-Juan Hou; Lan-Cui Liu; Yi-Ming Wei; Hua Liao (Environment, Development and Sustainability, 2023)

Numerical simulation and energy extraction power fitting of OWSCs under regular waves using SPH method - Xin Chen; Jie Cui; Ming-Yuan Li (Ocean Engineering, 2023)

Optimizing environmental flow based on a new optimization model in balancing objectives among river ecology, water supply and power generation in a high-latitude river - Peng Qi; Xiaoyu Tang; Y. Jun Xu; Zhen Cui; Jiaxin Sun; Guangxin Zhang; Yao Wu; Ming Jiang (Journal of Environmental Management, 2023)

Holocene provenance evolution of the northern South China Sea inferred from detrital zircon U-Pb geochronology and Hf isotopes - Ce Wang; David A. Foster; Ming Su; Yaping Lei; Letian Zeng; Heqi Cui (Global and Planetary Change, 2023)

Design of atomic cobalt selenide-doped sulfurized polyacrylonitrile cathode with enhanced electrochemical kinetics for high performance lithium-SPAN batteries - Zhi-Qiang Xu; Rong Zou; Wen-Wu Liu; Guang-Long Liu; Yun-Shou Cui; Yi-Xiao Lei; Ya-Wen Zheng; Wen-Jun Niu; You-Zhi Wu; Bing-Ni Gu; Ming-Jin Liu; Fen Ran; et al. (Chemical Engineering Journal, 2023)

The ionome and proteome landscape of aging in laying hens and relation to egg white quality - Guang Li; Yuqing Feng; Jian Cui; Qihang Hou; Tanfang Li; Meiting Jia; Zhengtian Lv; Qiuyu Jiang; Ying Wang; Ming Zhang; Lin Wang; Zengpeng Lv; et al. (Science China Life Sciences, 2023)

Non-monotonic Association Between Chlorinated Polyfluorinated Ether Sulfonic Acids Exposure and the Risk of Overweight/Obesity Status in Adults - Chu Chu; Qiu-Ling Fang; Xin-Xin Cui; Peng-Xin Dong; Zhengmin Qian; Stephen Edward McMillin; Steven W. Howard; Yan-Qiu Ou; Qing-Qing Li; Lu-Yin Wu; Li-Xia Liang; Shuang-Jian Qin; et al. (Exposure and Health, 2023)

Performance analysis of BDS-3 vehicle-/ship-/air-borne kinematic SPP/PPP/RTK - Yongxing Zhu; Feng Ming; Xianqiang Cui; Changsheng Cai; Xiaolin Jia (Advances in Space Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Fabrication of modified electrode by reduced graphene oxide (rGO) and polyaniline (PANI) for enhancing azo dye decolorization in bio-electrochemical systems (BESs) - Ai-Hong Chen; Yue-Jia Yang; Shuai Wang; Li-Ming Yang; Xue-Yun Gao; Dan Cui (Environmental Research, 2023)

Effect of a novel joint connection of UHPC wet joint and tapered sleeve locking-type couplers on the lateral cyclic response of precast segmental railway bridge columns - Yuxuan Wang; Zhao Cheng; Shuai Li; Jingquan Wang; Rui Zhong; Min Zeng; Fayan Ming; Bing Cui (Engineering Structures, 2023)

Fire resistance evaluation of laminated bamboo lumber column under eccentric compression - Zhaoyan Cui; Ming Xu; Ang Li; Liuhui Tu; Jia Zhu; Yurong Shen (Engineering Structures, 2023)

Evaluation of the respective contribution of anode and cathode for triclosan degradation in a bioelectrochemical system - Min-Hua Cui; Qian Zhang; John Justo Ambuchi; Lan-Ying Liu; Lei Chen; Shi-Ming Niu; Chao Zhang; Hong-Bo Liu; Chao Tie; Xue-Juan Bi; He Liu; Ai-Jie Wang (Bioresource Technology, 2023)

Loss of swallow tail sign on susceptibility-weighted imaging in neurosyphilis mimicking Alzheimer’s disease: a case report - Xiao-Li Cui; Shen Liu; Yi-Ming Zhang; Hong-Dong Zhao; Jian-Quan Shi (Acta Neurologica Belgica, 2023)

Numerical study of wedge entry in still water and waves using smoothed particle hydrodynamics methods - Jie Cui; Chang-Jun Gu; Xin Chen; Ming-Yuan Li; Bright Masvaya (Ocean Engineering, 2023)

Mixotrophic denitrification driven by plant carbon sources and influent sulphate for enhancing nitrogen removal in constructed wetlands - Chunhao Yan; Qibin Chen; Chaoxu Wang; Yong Wang; Jiayong Wang; Zuochen Li; Ming Yan; Yang Wei; Jianguo Cui (Journal of Water Process Engineering, 2023)

Activation of cellulose with CO2 and/or H2O: Evolution of functionalities of the biochar and environmental impacts - Cong Ming; Yuchen Jiang; Chao Li; Qifeng Chen; Shu Zhang; Shuang Wang; Bin Li; Zhenhua Cui; Yonggui Tang; Xun Hu (Biomass and Bioenergy, 2023)

GR1 and NTRA involved in pollen tube growth in the stigma of Arabidopsis - Ming Jun Zhang; Jing Jing Cui; Zi Ming Wang; Yu Xiu Dong; Xin-Qi Gao (Planta, 2023)

Long-term exposure to arsenic in drinking water leads to myocardial damage by oxidative stress and reduction in NO - Yi-Xin Cui; Lu Dong; Meng Zhang; Yi-Nan Liu; Yong-Hui Chen; Ming-Zhao Jia; Kun-Pan Chen; Hui Wang; Ya-Wen Shi; Tian-You Ma; Jing-Hong Chen (Toxicology, 2023)

Three new sesquilignans from the stems of Eleutherococcus senticosus and their bioactivities - Yue Zhang; Yi-Ming Zhao; Xiao-Jing Shao; Xue-Hui Wang; Tian-Tian Bei; Yi-Ran Jiang; Wen-Hui Xu; Hyun-Sun Lee; Meng-Xue Xiu; Jian Song; Long Cui (Phytochemistry Letters, 2023)

Rice genotypes and root-associated niches shifted bacterial community in response to pollution of di-(2-ethylhexyl) phthalate (DEHP) for promoting DEHP removal - Cui-Lan Zhu; Hui-Xiong Lü; Yu-Hong Huang; Ji-liang Cheng; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Lei Xiang; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

Evaluating the threshold limit value of acceptable exposure concentration for exposure to bioaerosols in a wastewater treatment plant: Reverse-quantitative microbial risk assessment and sensitivity analysis - Beibei Cui; Dongzi An; Haojun Li; Xi Luo; Hao Zhu; Ming Li; Xiaojun Ai; Jiaxin Ma; Wajid Ali; Cheng Yan (Journal of Hazardous Materials, 2023)

Facile synthesis of nitrogen-doped porous graphene for efficient adsorption of tetracycline: Behavior and mechanism - Hui Wang; Liang Shan; Wen Shi; Ming Wang; Guixiang Quan; Zourui Wang; Liqiang Cui; Jinlong Yan (Journal of Environmental Chemical Engineering, 2023)

The cotton protein GhIQD21 interacts with GhCaM7 and modulates organ morphogenesis in Arabidopsis by influencing microtubule stability - Xing Li; Li Wang; Yupeng Cui; Chen Liu; Yujie Liu; Lili Lu; Ming Luo (Plant Cell Reports, 2023)

A new chamigrane sesquiterpene from the rice fermentation of Antrodiella albocinnamomea - Min Guo; Ying-Zhong Liang; Xiu-Ming Cui; Lin-Jiao Shao; Yin-Fei Li; Xiao-Yan Yang (Natural Product Research, 2023)

Simultaneous ion fractionation and concentration by selectrodialysis for saline wastewater valorization - Zhenzhen Cui; Wenguang Wang; Yong Lin; Min Hu; Yuebiao Li; Boyu Pan; Ming Tan; Yang Zhang (Desalination, 2023)

Revealing the dynamic temperature of the cathode catalyst layer inside proton exchange membrane fuel cell by experimental measurements and numerical analysis - Qianqian Wang; Fumin Tang; Xiang Li; Jim P. Zheng; Liang Hao; Guomin Cui; Pingwen Ming (Chemical Engineering Journal, 2023)

Characterization of imidacloprid-induced hepatotoxicity and its mechanisms based on a metabolomic approach in Xenopus laevis - Xia Zhou; Renyue Ming; Meiting Guo; Hui Jiao; Honghao Cui; Deyu Hu; Ping Lu (Science of The Total Environment, 2023)

Insights on nitrogen and phosphorus removal mechanism in a single-stage Membrane Aeration Biofilm Reactor (MABR) dominated by denitrifying phosphorus removal coupled with anaerobic/aerobic denitrification - Ming Li; Xiwei Cao; Ziqing Wu; Jiaye Li; Ying Cui; Jun Liu; Baoan Li (Journal of Water Process Engineering, 2023)

Numerical investigations of the micro lunar dust particles deposition in the human oral respiratory airway - Xinguang Cui; Wei Song; Yuan Xue; Hanxiong Guan; Jinhua Zhang; Xinxing He; Honglei Ma; Ming Lei; Jintao Wang; Yichao Li (Journal of Hazardous Materials, 2023)

Smart contract design and process optimization of carbon trading based on blockchain: The case of China's electric power sector - Tian-yuan Zhang; Tian-tian Feng; Ming-li Cui (Journal of Cleaner Production, 2023)

The priming effects of plant leachates on dissolved organic matter degradation in water depend on leachate type and water stability - Yuan Cui; Jian-Qiao Meng; Yu-Han Chen; Fei-Fan Shao; Xuan-Zheng Chen; Yu Jin; Ming-Xiang Zhang; Guo Yun-Qian; Fang-Li Luo; Fei-Hai Yu (Environmental Research, 2023)

To what extent the traffic restriction policies can improve its air quality? An inspiration from COVID-19 - Si-qing Xu; Hong-di He; Ming-ke Yang; Cui-lin Wu; Xing-hang Zhu; Zhong-ren Peng; Yuya Sasaki; Kenji Doi; Shinji Shimojo (Stochastic Environmental Research and Risk Assessment, 2023)

Evaluation of the effect of biofilm formation on the reductive transformation of triclosan in cathode-modified electrolytic systems - Shi-Ming Niu; Qian Zhang; Thangavel Sangeetha; Lei Chen; Lan-Ying Liu; Ping Wu; Chao Zhang; Wei-Mon Yan; He Liu; Min-Hua Cui; Ai-Jie Wang (Science of The Total Environment, 2023)

Provenance and dispersal patterns of sediments on the continental shelf of northern South China Sea: Evidence from detrital zircon geochronology - Junmin Jia; Ce Wang; Ming Su; Wen Yan; Letian Zeng; Heqi Cui (Marine Geology, 2023)

Organics abatement and recovery from wastewater by a polymerization-based electrochemically assisted persulfate process: Promotion effect of chloride ion and its mechanism - Sui-Qin Yang; Zheng-Qian Liu; Yu-Hong Cui; Ming-Kui Wang (Journal of Hazardous Materials, 2023)

Arsenic metabolism, N6AMT1 and AS3MT single nucleotide polymorphisms, and their interaction on gestational diabetes mellitus in Chinese pregnant women - Xiaoshan Liang; Guanshuai Guo; Yiyun Wang; Meng Wang; Xi Chen; Jingran Zhang; Shuying Li; Liangpo Liu; Qingyu Huang; Bo Cui; Ming Zhang; Guifan Sun; et al. (Environmental Research, 2023)

Physical modelling of deformation and failure mechanisms and supporting effects for a deep-buried tunnel in inclined layered strata - Xiaoming Sun; Wenchao Zhao; Fuxin Shen; Jian Wang; Li Cui; Ming Jiang (Bulletin of Engineering Geology and the Environment, 2023)

Strength characteristics of rock anchored by NPR bolt with different preloads - Xiao-ming Sun; Li Cui; Yong Zhang; Lei Wang; Ming Jiang (Journal of Mountain Science, 2023)

Chronic Hemorrhagic Anemia Caused by Hookworm Infection: A Case Report - Baisheng Li; Shihong Chen; Xiangming Cui; Ming Dai; Wenying Meng; Qiong Wu; Huiming Sheng (Acta Parasitologica, 2023)

Sodium para-aminosalicylic acid ameliorates brain neuroinflammation and behavioral deficits in juvenile lead-exposed rats by modulating MAPK signaling pathway and alpha-synuclein - Zhao-cong Li; Yue-song Zhao; Jun-jie Lin; Lei-lei Wang; Han-xiao Song; Cui-liu Gan; Xiao-wei Zheng; Shi-yan Ou; Michael Aschner; Yue-ming Jiang; Jing-jing Luo; Yan Li (Toxicology Letters, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Adaptation of bacterial community in maize rhizosphere for enhancing dissipation of phthalic acid esters in agricultural soil - Yu-Hong Huang; Yu-Jie Yang; Xiaolian Wu; Cui-Lan Zhu; Huixiong Lü; Hai-Ming Zhao; Lei Xiang; Hui Li; Ce-Hui Mo; Yan-Wen Li; Quan-Ying Cai; Qing X. Li (Journal of Hazardous Materials, 2023)

Absence of water content contrast between lithosphere and asthenosphere in subduction zone - Yuto Sato; Eiichi Takahashi; Chang-Ming Xing; Li Li; Ze-Xian Cui; Wan-Feng Zhang; Xiao-Ping Xia (Earth and Planetary Science Letters, 2023)

A two-phase online air balancing method for multi-zone ventilation systems based on distributed finite-time control - Can Cui; Zhangjie Liu; Ming Li (Building and Environment, 2023)

Sodium Para-Aminosalicylic Acid Modulates Autophagy to Lessen Lead-Induced Neurodegeneration in Rat Cortex - Lei-lei Wang; Xiao-juan Zhu; Yuan-yuan Fang; Yan Li; Yue-song Zhao; Cui-liu Gan; Jing-jing Luo; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Neurotoxicity Research, 2023)

EMX2OS targeting IGF2BP1 represses Wilms’ tumour stemness, epithelial–mesenchymal transition and metastasis - Hong-Mei Zhang; Ming-Yu Cui; Zhi-Hong Chen (Journal of Genetics, 2023)

Early identification of strawberry leaves disease utilizing hyperspectral imaging combing with spectral features, multiple vegetation indices and textural features - Gangshan Wu; Yinlong Fang; Qiyou Jiang; Ming Cui; Na Li; Yunmeng Ou; Zhihua Diao; Baohua Zhang (Computers and Electronics in Agriculture, 2023)

E2F4 regulates cell cycle to mediate embryonic development in pigs - Wen-Jie Jiang; Ming-Hong Sun; Xiao-Han Li; Song-Hee Lee; Geun Heo; Dongjie Zhou; Xiang-Shun Cui (Theriogenology, 2023)

Bioactive diterpenoids and sesquiterpenoids with different skeletons from Salvia digitaloides Diels - Xu Liu; Xiao-Qing Zhan; Mei-Jie Wang; Wen-Bo Cui; Xiao-Han Chen; Feng-Ming Qi; Jian-Ning Yu; Jian-Ye Dai; Dong-Qing Fei; Zhan-Xin Zhang (Phytochemistry, 2023)

Optical diagnostics of methanol active-thermal atmosphere combustion in compression ignition engine - Mingsheng Wen; Haifeng Liu; Yanqing Cui; Zhenyang Ming; Lei Feng; Mingfa Yao (Fuel, 2023)

Biochemical, histopathological and untargeted metabolomic analyses reveal hepatotoxic mechanism of acetamiprid to Xenopus laevis - Hui Jiao; Tingting Yuan; Xiaohuan Wang; Xia Zhou; Renyue Ming; Honghao Cui; Deyu Hu; Ping Lu (Environmental Pollution, 2023)

Heme-oxygenase-1 as a target for phthalate-induced cardiomyocytes ferroptosis - Jia-Xin Wang; Yi Zhao; Ming-Shan Chen; Hao Zhang; Jia-Gen Cui; Jin-Long Li (Environmental Pollution, 2023)

Passivation of positively charged cationic defects in perovskite with nitrogen-donor crown ether enabling efficient perovskite solar cells - Yuxuan Yang; Tao Zhao; Ming-Hua Li; Xiaoxue Wu; Mingyue Han; Shih-Chi Yang; Qiaoling Xu; Lede Xian; Xiang Chi; Ning-Jiu Zhao; Hong Cui; Sihan Li; et al. (Chemical Engineering Journal, 2023)

Chemical looping partial oxidation (CLPO) of toluene on LaFeO3 perovskites for tunable syngas production - Yi Lv; Binhai Cheng; Hang Yang; Xiaomin Cui; Ming Zhao (Chemical Engineering Journal, 2023)

Provenance of sediments in the northern Manila Trench: An assessment from detrital zircon geochronology - Ce Wang; Heqi Cui; Letian Zeng; Ming Su (Science China Earth Sciences, 2023)

Therapeutic Effects of Human Pluripotent Stem Cell-Derived Mesenchymal Stem Cells on a Murine Model of Acute Type-2-Dominated Airway Inflammation - Si-Yuan Ma; Ning Zhao; Lele Cui; Ying Li; Hang Zhang; Jing Wang; Jie Pang; Ming Wang; Chengshuo Wang; Sun Ying; Zi-Bing Jin; Luo Zhang (Stem Cell Reviews and Reports, 2022)

Increasing soil heterogeneity strengthens the inhibition of a native woody plant by an invasive congener - Yi Hu; Zhen-Wei Xu; Ming-Yan Li; Jordan R. Croy; Zhong-Yi Zhang; Hai-Mei Li; Wei-Hua Guo; Xiao-Lei Jiang; Hui-Cui Lu; Xiao Guo (Plant and Soil, 2022)

What are the disease burden and its sensitivity analysis of workers exposing to Staphylococcus aureus bioaerosol during warm and cold periods in a wastewater treatment plant? - Jiaxin Ma; Dongzi An; Beibei Cui; Manli Liu; Hao Zhu; Ming Li; Xiaojun Ai; Wajid Ali; Cheng Yan (Environmental Science and Pollution Research, 2022)

Paenibacillus hamazuiensis sp. nov., a bacterium isolated from Hamazui hot spring in Yunnan province, south-west China - Juan Wang; Ming Deng; En-Min Zhou; Lei Ran; Cui-Ping Miao; Yi-Qing Li; Jun-Mei Ding; Shu-Kun Tang (Archives of Microbiology, 2022)

Revealing top-k dominant individuals in incomplete data based on spark environment - Ke Wang; Binge Cui; Jerry Chun-Wei Lin; Jimmy Ming-Tai Wu (Environment, Development and Sustainability, 2022)

Land-use transition and its driving forces in a minority mountainous area: a case study from Mao County, Sichuan Province, China - Yizhen Zhao; Ming Zhang; Jianjun Cui (Environmental Monitoring and Assessment, 2022)

Tract-specific white matter microstructural alterations in subjects with schizophrenia and unaffected first-degree relatives - Sangma Xie; Junjie Zhuo; Ming Song; Congying Chu; Yue Cui; Yunchun Chen; Huaning Wang; Lihua Li; Tianzi Jiang (Brain Imaging and Behavior, 2022)

Screening for SH3TC2 variants in Charcot–Marie–Tooth disease in a cohort of Chinese patients - Bo Sun; Zheng-Qing He; Yan-Ran Li; Jiong-Ming Bai; Hao-Ran Wang; Hong-Fen Wang; Fang Cui; Fei Yang; Xu-Sheng Huang (Acta Neurologica Belgica, 2022)

Effects of secondary succession on soil fungal and bacterial compositions and diversities in a karst area - Genzhu Wang; Yuguo Liu; Ming Cui; Ziyuan Zhou; Qian Zhang; Yajin Li; Wenxiu Ha; Danbo Pang; Jiufu Luo; Jinxing Zhou (Plant and Soil, 2022)

Correction to: Sox10 Gene Is Required for the Survival of Saccular and Utricular Hair Cells in a Porcine Model - Jing-cui Qi; Qing-qing Jiang; Long Ma; Shuo-long Yuan; Wei Sun; Li-sheng Yu; Wei-wei Guo; Shi-ming Yang (Molecular Neurobiology, 2022)

Sox10 Gene Is Required for the Survival of Saccular and Utricular Hair Cells in a Porcine Model - Jing-cui Qi; Qing-qing Jiang; Long Ma; Shuo-long Yuan; Wei Sun; Li-sheng Yu; Wei-wei Guo; Shi-ming Yang (Molecular Neurobiology, 2022)

Combined game model and investment decision making of power grid-distributed energy system - Yongxiu He; Wei Xiong; Binyou Yang; Hai-yan Yang; Jiu-fang Zhou; Ming-li Cui; Yan Li (Environment, Development and Sustainability, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

High expression of HOXB3 predicts poor prognosis and correlates with tumor immunity in lung adenocarcinoma - Ming Yan; Xiaojun Yin; Luan Zhang; Yuanbo Cui; Xiwen Ma (Molecular Biology Reports, 2022)

A New Species of Paradiplozoon (Monogenea: Diplozoidae), A Gill Parasite of the Schizothorax Fish (Cyprinidae: Schizothoracinae) from the Yarkand River, Xinjiang, China - Kadirden Arken; Cui-Lan Hao; Ai-Ming Guo; Wen-Run Zhang; Meng-Jie Rong; Wuljan Kamal; Sheng-Li Tian; Munira Kadir; Cheng Yue (Acta Parasitologica, 2022)

FHA domain of AGGF1 is essential for its nucleocytoplasmic transport and angiogenesis - Cui-Fang Zhang; Han-Ming Wang; Andong Wu; Yang Li; Xiao-Li Tian (Science China Life Sciences, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Higher photocatalytic removal of organic pollutants using pangolin-like composites made of 3–4 atomic layers of MoS2 nanosheets deposited on tourmaline - Ming Hao; Hao Li; Li Cui; Wei Liu; Baizeng Fang; Jinsheng Liang; Xinlei Xie; Dongxu Wang; Fei Wang (Environmental Chemistry Letters, 2021)

Shared and specific patterns of structural and functional thalamo-frontal disturbances in manic and euthymic pediatric bipolar disorder - Yi-Bing Guo; Wei-Jia Gao; Zhi-Liang Long; Wei-Fang Cao; Dong Cui; Yong-Xin Guo; Qing Jiao; Jian-Feng Qiu; Lin-Yan Su; Guang-Ming Lu (Brain Imaging and Behavior, 2021)
Bipolar disorder (BD) is clinically defined by alternating depressive and manic episodes with a separated period of euthymia. Thalamo-frontal loop plays vital role in psychotic symptoms, altered motor control and executive difficulties in BD. It remains unclear that structural and functional alterations of thalamo-frontal loop among the different mood states in BD, especially in pediatric BD(PBD). Twenty manic PBD (mPBD), 20 euthymic PBD (ePBD) and 19 healthy controls (HCs) were included in the study. By analyzing the T1 images and fMRI signals, thalamus volume and frontal grey matter cortical thickness were tested, and functional connectivity (FC) between bilateral thalamus and frontal cortex was calculated. Relationship between clinical indices and thalamo-frontal FC was also evaluated in mPBD and ePBD adolescents. Compared to HCs, the cortical thickness of left middle frontal gyrus (MFG), bilateral superior frontal gyrus (SFG) was significantly decreased in both mPBD and ePBD patients, and volume of left thalamus and cortical thickness of right MFG significantly decreased in mPBD patients. Compared to that of the HCs and ePBD subjects, thalamo-frontal hyperconnectivity with MFG was found in mPBD, and compared with that of HCs, thalamo-frontal hypoconnectivity with precentral gyrus/SFG was found in ePBD. In ePBD patients, episode times positively correlated with FC values between thalamus and precentral gyrus. The findings of the present study demonstrate detailed knowledge regarding shared and specific structural and functional disruption in thalamo-frontal loop in mPBD and ePBD subjects. Thalamo-frontal abnormalities reported in adult BD subjects were also observed in adolescent BD patients, and thalamo-frontal dysfunction may be a crucial treatment target in BD.

Association between large artery stenosis, cerebral small vessel disease and risk of ischemic stroke - Fei Han; Ding-Ding Zhang; Fei-Fei Zhai; Jun Xue; Jiang-Tao Zhang; Shuang Yan; Li-Xin Zhou; Jun Ni; Ming Yao; Meng Yang; Ming-Li Li; Zheng-Yu Jin; et al. (Science China Life Sciences, 2021)

Comprehensive plasma metabolomic and lipidomic analyses reveal potential biomarkers for heart failure - Juntuo Zhou; Xi Chen; Wei Chen; Lijun Zhong; Ming Cui (Molecular and Cellular Biochemistry, 2021)

Geomorphic effect of debris-flow sediments on the Min River, Wenchuan Earthquake region, western China - Xu-dong Hu; Li-qin Zhou; Wei-ming Liu; Hao Wang; Lei Cui (Journal of Mountain Science, 2021)

Velocity profile of debris flow based on quadratic rheology model - Cui Du; Wei-ming Wu; Chao Ma (Journal of Mountain Science, 2021)

Effects of different temperatures on seawater acclimation in rainbow trout Oncorhynchus mykiss: osmoregulation and branchial phospholipid fatty acid composition - Jian Ge; Ming Huang; Yangen Zhou; Chengyue Liu; Cui Han; Qinfeng Gao; Yunwei Dong; Shuanglin Dong (Journal of Comparative Physiology B, 2021)

Sphingopyxis microcysteis sp. nov., a novel bioactive exopolysaccharides-bearing Sphingomonadaceae isolated from the Microcystis phycosphere - Xiao-ling Zhang; Gui-xian Li; Ya-ming Ge; Nurhezreen Md Iqbal; Xi Yang; Zhen-dong Cui; Qiao Yang (Antonie van Leeuwenhoek, 2021)

Amygdala-based Functional Network Reveals Dissociated Neural Correlates of Consensual and Idiosyncratic Emotional Movie Experiences - Lin Cui; Bingbing Guo; Dan Zhao; Jiaxin Li; Yu Luo; Ming Meng (Neuroscience Bulletin, 2021)

Synthesis and antitumor evaluation of (aryl)methyl-amine derivatives of dehydroabietic acid-based B ring-fused-thiazole as potential PI3K/AKT/mTOR signaling pathway inhibitors - Nai-Yuan Chen; Yu-Lan Xie; Guo-Dong Lu; Fang Ye; Xin-Yu Li; Yu-Wen Huang; Ming-Li Huang; Tie-Yu Chen; Cui-Ping Li (Molecular Diversity, 2021)

Design, synthesis and evaluation of dihydrotriazine derivatives-bearing 5-aryloxypyrazole moieties as antibacterial agents - Tian-Yi Zhang; Chun-Shi Li; Ming-Yue Cui; Xue-Qian Bai; Jiang-Hui Chen; Ze-Wen Song; Bo Feng; Xue-Kun Liu (Molecular Diversity, 2021)

Diversity, metabolism and cultivation of archaea in mangrove ecosystems - Cui-Jing Zhang; Yu-Lian Chen; Yi-Hua Sun; Jie Pan; Ming-Wei Cai; Meng Li (Marine Life Science & Technology, 2021)

The spatial distribution characteristics of coseismic landslides triggered by the Ms7.0 Lushan earthquake and Ms7.0 Jiuzhaigou earthquake in southwest China - Ming Chang; Peng Cui; Lu Xu; Yu Zhou (Environmental Science and Pollution Research, 2021)

Combined effects of arbuscular mycorrhizae fungus and composted pig manure on the growth of ryegrass and uptake of Cd and Zn in the soil from an e-waste recycling site - Jun Meng; Zhonghua Cui; Henglei Zhang; Jin Zhang; Xianjin Tang; Ming Hung Wong; Shengdao Shan (Environmental Science and Pollution Research, 2021)

Design and Characterization of a Novel Hybrid Antimicrobial Peptide OM19R Based on Oncocin and MDAP-2 - Lei Liu; Jie Liu; Qi Cui; Bo-Yan Jia; Zhi-Hua Pei; Kokou Ayefounin Odah; Yi-Ming Wang; Wen-Long Dong; Ling-Cong Kong; Hong-Xia Ma (International Journal of Peptide Research and Therapeutics, 2020)

Soil bio-cementation using an improved 2-step injection method - Ming-Juan Cui; Jun-Jie Zheng; Rong-Jun Zhang; Han-Jiang Lai (Arabian Journal of Geosciences, 2020)

Rhizobium inoculation alleviates separate and combined toxicities of Na+ and Cl– in alfalfa - Lichao Sheng; Guangjuan Cui; Ming Luo; Jiandong Sheng; Xiurong Wang (Acta Physiologiae Plantarum, 2020)

Synthesis and molecular docking studies of novel pyrimidine derivatives as potential antibacterial agents - Xue-Qian Bai; Chun-Shi Li; Ming-Yue Cui; Ze-Wen Song; Xing-Yu Zhou; Chao Zhang; Yang Zhao; Tian-Yi Zhang; Tie-Yan Jiang (Molecular Diversity, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Selenium accumulation characteristics of Cyphomandra betacea (Solanum betaceum) seedlings - Linjin Lin; Jing Sun; Tonghao Cui; Xiong Zhou; Ming’an Liao; Yunmin Huan; Liu Yang; Caifang Wu; Xianmin Xia; Yuxi Wang; Zhiyu Li; Jinpeng Zhu; et al. (Physiology and Molecular Biology of Plants, 2020)

Correction to: Simulated microgravity significantly altered metabolism in epidermal stem cells - Bin-Bin Li; Zheng-Yang Chen; Nan Jiang; Song Guo; Jia-Qi Yang; Shao-Bin Chai; Hong-Feng Yan; Pei-Ming Sun; Gang Hu; Tao Zhang; Bing-Xin Xu; Hong-Wei Sun; et al. (In Vitro Cellular & Developmental Biology - Animal, 2020)

Accumulation of Cu, Cd, Pb, Zn and total P from synthetic stormwater in 30 bioretention plants - Ying Mei; Hang Zhou; Long Gao; Yi-Ming Zuo; Kun-Hao Wei; Na-Qi Cui (Environmental Science and Pollution Research, 2020)

MicroRNA-625-5p Sponges lncRNA MALAT1 to Inhibit Cervical Carcinoma Cell Growth by Suppressing NF-κB Signaling - Yujiao Li; Yumei Ding; Ning Ding; Hong Zhang; Ming Lu; Xiaorong Cui; Xiaohui Yu (Cell Biochemistry and Biophysics, 2020)

Thioredoxin-Interacting Protein (TXNIP) Regulates Parkin/PINK1-mediated Mitophagy in Dopaminergic Neurons Under High-glucose Conditions: Implications for Molecular Links Between Parkinson’s Disease and Diabetes - Cun-Jin Su; Zhu Shen; Ru-Xiao Cui; Ya Huang; De-Lai Xu; Feng-Lun Zhao; Jie Pan; Ai-Ming Shi; Tong Liu; Yun-Li Yu (Neuroscience Bulletin, 2020)

Simulated microgravity significantly altered metabolism in epidermal stem cells - Bin-Bin Li; Zheng-Yang Chen; Nan Jiang; Song Guo; Jia-Qi Yang; Shao-Bin Chai; Hong-Feng Yan; Pei-Ming Sun; Gang Hu; Tao Zhang; Bing-Xin Xu; Hong-Wei Sun; et al. (In Vitro Cellular & Developmental Biology - Animal, 2020)
Simulated microgravity can significantly affect various cell types and multiple systems of the human body, such as cardiovascular system, skeletal muscle system, and immune system, and is known to cause anemia and loss of electrolyte and fluids. Epidermal stem cells (EpSCs) were cultured in a rotary cell culture system (RCCS) bioreactor to simulate microgravity. The metabolites of EpSCs were identified by liquid chromatography-mass spectrometry (LC-MS). Compared with normal gravity (NG) group, a total of 57 different metabolites of EpSCs were identified ( P < 0.05, VIP > 1), including lipids and lipid-like molecules (51 molecules), amino acids (5 molecules), nucleosides, nucleotides, and analogues (1 molecule). According to the partial least squares discriminant analysis (PLS-DA) score plot, a VIP > 1 and P < 0.05 were obtained for the 57 different metabolites, of which 23 molecules were significantly downregulated and 34 were significantly upregulated in simulated microgravity (SMG) group. These results showed that SMG has a significant impact on different pathways, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis indicated that multiple pathways were involved, mainly the amino acid metabolism pathway, lipid metabolism pathway, membrane transport pathway, and cell growth and death pathways. Thus, the metabolic profile of EpSCs was changed under SMG. Exploring the metabolic profile of EpSCs would be helpful to further understand the growth characteristics of EpSCs under SMG, which will provide a new approach to explore the metabolomics mechanism of stress injury and repair trauma under SMG.

ABNORMAL FLOWER AND GRAIN 1 encodes OsMADS6 and determines palea identity and affects rice grain yield and quality - Xiaoqi Yu; Saisai Xia; Qiankun Xu; Yuanjiang Cui; Ming Gong; Dali Zeng; Qiang Zhang; Lan Shen; Guiai Jiao; Zhenyu Gao; Jiang Hu; Guangheng Zhang; et al. (Science China Life Sciences, 2020)

Bifidobacterium bifidum TMC3115 Can Characteristically Influence Glucose and Lipid Profile and Intestinal Microbiota in the Middle-Aged and Elderly - Ke Wang; Xiaohong Yu; Yi Li; Yun Guo; Lin Ge; Fangfang Pu; Xinying Ma; Wenjing Cui; Francesco Marrota; Fang He; Ming Li (Probiotics and Antimicrobial Proteins, 2019)

In situ meta‐omic insights into the community compositions and ecological roles of hadal microbes in the Mariana Trench - Zhao‐Ming Gao; Jiao‐Mei Huang; Guo‐Jie Cui; Wen‐Li Li; Jun Li; Zhan‐Fei Wei; Jun Chen; Yong‐Zhi Xin; Du‐Si Cai; Ai‐Qun Zhang; Yong Wang (Environmental Microbiology, 2019)
Summary The low temperature and elevated hydrostatic pressure in hadal trenches at water depths below 6000 m render sample collection difficult. Here, in situ hadal water microbial samples were collected from the Mariana Trench and analysed. The hadal microbial communities at different depths were revealed to be consistent and were dominated by heterotrophic Marinimicrobia. Thirty high‐quality metagenome‐assembled genomes (MAGs) were retrieved to represent the major hadal microbes affiliated with 12 prokaryotic phyla. Most of the MAGs were newly reported and probably derived from novel hadal inhabitants as exemplified by a potentially new candidate archaeal phylum in the DPANN superphylum. Metabolic reconstruction indicated that a great number of the MAGs participated in nitrogen and sulfur cycling, in which the nitrification process was driven sequentially by Thaumarchaeota and Nitrospirae and sulfur oxidization by Rhodospirillales in the Alphaproteobacteria class. Moreover, several groups of hadal microbes were revealed to be potential carbon monoxide oxidizers. Metatranscriptomic result highlighted the contribution of Chloroflexi in degrading recalcitrant dissolved organic matter and Marinimicrobia in extracellular protein decomposition. The present work provides an in‐depth view on the hadal microbial communities regarding their endemism and element cycles.

Modeling Long-Wavelength Geoid Anomalies from Instantaneous Mantle Flow: Results from Two Recent Tomography Models - Ronghua Cui; Jian Fang; Masaki Yoshida; Ming Chen (Pure and Applied Geophysics, 2019)

microRNA-7 inhibition protects human osteoblasts from dexamethasone via activation of epidermal growth factor receptor signaling - Jian-bo Fan; Wei Liu; Xin-hui Zhu; Sheng-yu Cui; Zhi-ming Cui; Jian-ning Zhao (Molecular and Cellular Biochemistry, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

Terretonin D1, a new meroterpenoid from marine-derived Aspergillus terreus ML-44 - Chang-Jing Wu; Xiang Cui; Biao Xiong; Ming-Sheng Yang; Yun-Xia Zhang; Xiao-Meng Liu (Natural Product Research, 2019)

Towards understanding the biosynthetic pathway for ustilaginoidin mycotoxins in Ustilaginoidea virens - Yuejiao Li; Ming Wang; Zhaohui Liu; Kang Zhang; Fuhao Cui; Wenxian Sun (Environmental Microbiology, 2019)
Summary Ustilaginoidins, toxic to plants, animals and human, are one of major types of mycotoxins produced by Ustilaginoidea virens . In this study, a gene cluster containing the polyketide synthase gene UvPKS1 was analysed via gene replacement and biochemical studies to determine ustilaginoidin biosynthetic pathway in U. virens . UvPKS1 was first proven to be responsible for the first step of ustilaginoidin biosynthesis, since neither ustilaginoidin derivatives nor intermediates were produced when UvPKS1 was deleted. Replacement of ugsO greatly reduced ustilaginoidin production but increased the ratios of dehydrogenated/hydrogenated ustilagioidin derivatives. The enhanced growth rate of the Δ ugsO mutant indicates that accumulation of certain ustilaginoidin derivatives may adversely affect mycelial growth in U. virens . Deletion of ugsT encoding a putative MFS transporter disrupted the ability to generate ustilaginoidins. The ustilaginoidin derivatives produced in the Δ ugsJ mutant all lack C3‐methyl, indicating that UgsJ is responsible for C3‐methylation. Only monomeric intermediates, such as 3‐methyl‐dihydro‐nor‐rubrofusarin, but no ustilaginoidin derivatives were generated in the Δ ugsL mutant, indicating that UgsL is responsible for the dimerization of nor‐rubrofusarin derivatives to produce ustilaginoidins. However, ugsR2 deletion had no dramatic effect on ustilaginoidin biosynthesis. Together, biochemical analyses with bioinformatics and chemoinformatics uncover a multiple‐step enzyme‐catalysed pathway for ustilaginoidin biosynthesis in U. virens .

Two new sesquiterpenes from cultures of the higher fungus Pholiota nameko - Xiao-Yan Yang; Wan-Rong Niu; Rui-Ting Li; Xiu-Ming Cui; Ji-Kai Liu (Natural Product Research, 2019)

Benthic foraminiferal fauna and sediment provenance of Eocene syn-rift sequences in Taiwan: implication for onset of Asian epi-continental marginal seas off China coast - Chi-Yue Huang; Lei Shao; Ming-Huei Wang; Wei-Guang Xue; Pei-Jun Qiao; Yu-Chi Cui; Yuan-Li Hou (Marine Geophysical Research, 2019)

Crosstalk Between Inflammation and Glutamate System in Depression: Signaling Pathway and Molecular Biomarkers for Ketamine’s Antidepressant Effect - Wenyan Cui; Yuping Ning; Wu Hong; Ju Wang; Zhening Liu; Ming D. Li (Molecular Neurobiology, 2019)

Influence of inflow discharge and bed erodibility on outburst flood of landslide dam - Ming-jun Zhou; Gordon G. D. Zhou; Kahlil Fredrick E. Cui; Dong-ri Song; Xue-qiang Lu (Journal of Mountain Science, 2019)

Habitat selection of wintering cranes (Gruidae) in typical lake wetland in the lower reaches of the Yangtze River, China - Cheng Wang; Bin Dong; Ming Zhu; Hui Huang; Yu-huang Cui; Xiang Gao; Li-ping Liu (Environmental Science and Pollution Research, 2019)

The complete chloroplast genome of the threatened Dipentodon sinicus (Dipentodontaceae) - Ming-Tai An; Xing-Yong Cui; Jia-Xin Yang; Guo-Xiong Hu (Journal of Genetics, 2019)

Chronic Intracerebroventricular Infusion of Metformin Inhibits Salt-Sensitive Hypertension via Attenuation of Oxidative Stress and Neurohormonal Excitation in Rat Paraventricular Nucleus - Xiao-Jing Yu; Ya-Nan Zhao; Yi-Kang Hou; Hong-Bao Li; Wen-Jie Xia; Hong-Li Gao; Kai-Li Liu; Qing Su; Hui-Yu Yang; Bin Liang; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Genomics insights into ecotype formation of ammonia‐oxidizing archaea in the deep ocean - Yong Wang; Jiao‐Mei Huang; Guo‐Jie Cui; Takuro Nunoura; Yoshihiro Takaki; Wen‐Li Li; Jun Li; Zhao‐Ming Gao; Ken Takai; Ai‐Qun Zhang; Ramunas Stepanauskas (Environmental Microbiology, 2019)
Summary Various lineages of ammonia‐oxidizing archaea (AOA) are present in deep waters, but the mechanisms that determine ecotype formation are obscure. We studied 18 high‐quality genomes of the marine group I AOA lineages (alpha, gamma and delta) from the Mariana and Ogasawara trenches. The genomes of alpha AOA resembled each other, while those of gamma and delta lineages were more divergent and had even undergone insertion of some phage genes. The instability of the gamma and delta AOA genomes could be partially due to the loss of DNA polymerase B ( polB) and methyladenine DNA glycosylase ( tag ) genes responsible for the repair of point mutations. The alpha AOA genomes harbour genes encoding a thrombospondin‐like outer membrane structure that probably serves as a barrier to gene flow. Moreover, the gamma and alpha AOA lineages rely on vitamin B 12 ‐independent MetE and B 12 ‐dependent MetH, respectively, for methionine synthesis. The delta AOA genome contains genes involved in uptake of sugar and peptide perhaps for heterotrophic lifestyle. Our study provides insights into co‐occurrence of cladogenesis and anagenesis in the formation of AOA ecotypes that perform differently in nitrogen and carbon cycling in dark oceans.

A new polyketide purpurogenic acid: the activated production of polyketides by the diethyl sulphate mutagenesis of marine-derived Penicillium purpurogenum G59 - Ming-Wen Xia; Yu Yang; Rui Xu; Chang-Wei Li; Cheng-Bin Cui (Natural Product Research, 2019)

Correlation between S100A11 and the TGF-β1/SMAD4 pathway and its effects on the proliferation and apoptosis of pancreatic cancer cell line PANC-1 - Yi-Fei Ji; Tao Li; Feng Jiang; Wen-Kai Ni; Cheng-Qi Guan; Zhao-Xiu Liu; Cui-Hua Lu; Run-Zhou Ni; Wei Wu; Ming-Bing Xiao (Molecular and Cellular Biochemistry, 2019)

Insights into the effect of chemical treatment on the physicochemical characteristics and adsorption behavior of pig manure-derived biochars - Rong-Zhong Wang; Dan-Lian Huang; Chen Zhang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Xiao-Min Gong; Min Cheng; Jia Wan; Qing Zhang (Environmental Science and Pollution Research, 2019)

β2-AR regulates the expression of AKR1B1 in human pancreatic cancer cells and promotes their proliferation via the ERK1/2 pathway - Ming-Bing Xiao; Dan-Dan Jin; Yu-Jie Jiao; Wen-Kai Ni; Jin-Xia Liu; Li-Shuai Qu; Cui-Hua Lu; Run-Zhou Ni; Feng Jiang; Wei-Chang Chen (Molecular Biology Reports, 2018)

Cryo-EM structure reveals cylindrical nucleocapsids from two polydnaviruses - Ji-Hui Cui; Ya-Bin Chen; Ming Li; Qiu-Chen Cai; Li-Dan Zhang; Zi-Yun Lu; Jian-Cheng Li; Qi-Shun Zhu; Gang Ji; Kai-Jun Luo (Archives of Virology, 2018)

Boron Affects the Development of the Kidney Through Modulation of Apoptosis, Antioxidant Capacity, and Nrf2 Pathway in the African Ostrich Chicks - Haseeb Khaliq; Wang Jing; Xiao Ke; Yang Ke-Li; Sun Peng-peng; Lei Cui; Qiu Wei-wei; Lei Zhixin; Liu Hua-Zhen; Song Hui; Zhong Ju-Ming; Peng Ke-Mei (Biological Trace Element Research, 2018)

Brain Network Studies in Chronic Disorders of Consciousness: Advances and Perspectives - Ming Song; Yujin Zhang; Yue Cui; Yi Yang; Tianzi Jiang (Neuroscience Bulletin, 2018)

Manipulating Aeroponically Grown Potatoes with Gibberellins and Calcium Nitrate - Cui-Cun Wang; Xi-Yao Wang; Ke-Xiu Wang; Jian-Jun Hu; Ming-Xia Tang; Wei He; Peter Vander Zaag (American Journal of Potato Research, 2018)

Competition and habitat filtering jointly explain phylogenetic structure of soil bacterial communities across elevational gradients - Qian Zhang; Marta Goberna; Yuguo Liu; Ming Cui; Haishui Yang; Qixiang Sun; Heribert Insam; Jinxing Zhou (Environmental Microbiology, 2018)
Summary The importance of assembly processes in shaping biological communities is poorly understood, especially for microbes. Here, we report on the forces that structure soil bacterial communities along a 2000 m elevational gradient. We characterized the relative importance of habitat filtering and competition on phylogenetic structure and turnover in bacterial communities. Bacterial communities exhibited a phylogenetically clustered pattern and were more clustered with increasing elevation. Biotic factors (i.e., relative abundance of dominant bacterial lineages) appeared to be most important to the degree of clustering, evidencing the role of the competitive ability of entire clades in shaping the communities. Phylogenetic turnover showed the greatest correlation to elevation. After controlling the elevation, biotic factors showed greater correlation to phylogenetic turnover than all the habitat variables (i.e., climate, soil and vegetation). Structural equation modelling also identified that elevation and soil organic matter exerted indirect effects on phylogenetic diversity and turnover by determining the dominance of microbial competitors. Our results suggest that competition among bacterial taxa induced by soil carbon contributes to the phylogenetic pattern across elevational gradient in the Tibetan Plateau. This highlights the importance of considering not only abiotic filtering but also biotic interactions in soil bacterial communities across stressful elevational gradients.

Ethanol extract of Rehmannia glutinosa exerts antidepressant-like effects on a rat chronic unpredictable mild stress model by involving monoamines and BDNF - Jun-Ming Wang; Li-Xin Pei; Yue-Yue Zhang; Yong-Xian Cheng; Chun-Ling Niu; Ying Cui; Wei-Sheng Feng; Gui-Fang Wang (Metabolic Brain Disease, 2018)

Optimized staggered-grid finite-difference operators using window functions - Ying-Jun Ren; Jian-Ping Huang; Peng Yong; Meng-Li Liu; Chao Cui; Ming-Wei Yang (Applied Geophysics, 2018)

Toxic effect and mechanism of four ionic liquids on seedling taproots of Arabidopsis thaliana - Ming Li; Yonglai Xue; Zhenjiang Liu; Jin Guo; Liyun Liu; Yuanyuan Zhang; Lu Gao; Lizhao Wang; Yin Cui; Daolin Du (Environmental Science and Pollution Research, 2018)

Responses of soil microbial community to nitrogen fertilizer and precipitation regimes in a semi-arid steppe - Yi-Fei Sun; Ju-Pei Shen; Cui-Jing Zhang; Li-Mei Zhang; Wen-Ming Bai; Ying Fang; Ji-Zheng He (Journal of Soils and Sediments, 2018)

Design, synthesis and anti-cancer evaluation of novel podophyllotoxin derivatives as potent tubulin-targeting agents - Cui Hu; Xiang Zhu; Gu-Hao Wang; Xun Wu; Hong-Wei Han; Gui-Hua Lu; Jin-Liang Qi; Yan-Jun Pang; Rong-Wu Yang; Xiao-Ming Wang; Yong-Hua Yang (Medicinal Chemistry Research, 2018)

Nrf2/ARE pathway inhibits ROS-induced NLRP3 inflammasome activation in BV2 cells after cerebral ischemia reperfusion - Xiujian Xu; Liang Zhang; Xinchun Ye; Qi Hao; Tao Zhang; Guiyun Cui; Ming Yu (Inflammation Research, 2018)

Soft rot disease alters soil characteristics and root-associated, culturable microbial community of Amorphophallus konjac - Fei He; Zhongliang Zhang; Ming Cui; Lieping Liu; Quanhong Xue (Journal of General Plant Pathology, 2018)

Miscanthus sp.: Genetic Diversity and Phylogeny in China - Chunxia Ge; Xiuming Liu; Shimin Liu; Jing Xu; Hongfei Li; Tengteng Cui; Yao Yao; Ming Chen; Weili Yu; Cuixia Chen (Plant Molecular Biology Reporter, 2017)

Shear wave velocity prediction during CO2-EOR and sequestration in the Gao89 well block of the Shengli Oilfield - Lin Li; Jin-Feng Ma; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu (Applied Geophysics, 2017)

Re-evaluate the Efficacy and Safety of Human Urinary Kallidinogenase (RESK): Protocol for an Open-Label, Single-Arm, Multicenter Phase IV Trial for the Treatment of Acute Ischemic Stroke in Chinese Patients - Jun Ni; Jiazhi Qu; Ming Yao; Zhijun Zhang; Xihua Zhong; Liying Cui (Translational Stroke Research, 2017)

Anti-glomerular basement membrane glomerulonephritis with thrombotic microangiopathy: a case report - Xiao-juan Yu; Sha-sha Han; Su-xia Wang; Xiao-yu Jia; Wei-yi Guo; Zhao Cui; Feng Yu; Fu-de Zhou; Ming-hui Zhao (Immunologic Research, 2017)

Arsenic sorption by red mud-modified biochar produced from rice straw - Chuan Wu; Liu Huang; Sheng-Guo Xue; Yu-Ying Huang; William Hartley; Meng-qian Cui; Ming-Hung Wong (Environmental Science and Pollution Research, 2017)

Response mechanism of post-earthquake slopes under heavy rainfall - Hong-zhi Qiu; Ji-ming Kong; Ren-chao Wang; Yun Cui; Sen-wang Huang (Journal of Seismology, 2017)

Koninginins R-S from the endophytic fungus Trichoderma koningiopsis - Ming Hu; Qi-Ling Li; Ya-Bin Yang; Kai Liu; Cui-Ping Miao; Li-Xing Zhao; Zhong-Tao Ding (Natural Product Research, 2017)

Effects of Spartina alterniflora Invasion on the Abundance, Diversity, and Community Structure of Sulfate Reducing Bacteria along a Successional Gradient of Coastal Salt Marshes in China - Jun Cui; Xueping Chen; Ming Nie; Shubo Fang; Boping Tang; Zhexue Quan; Bo Li; Changming Fang (Wetlands, 2017)

Implementation of the strain hardening model into buffer material in high level waste repository - Lu Chen; Lan Qiao; Ming Cui; Qingwen Li (Geosciences Journal, 2017)

Population structure and diversity of citrus tristeza virus (CTV) isolates in Hunan province, China - Cui Xiao; Run-Xian Yao; Fang Li; Su-Ming Dai; Grazia Licciardello; Antonino Catara; Alessandra Gentile; Zi-Niu Deng (Archives of Virology, 2017)

Gastroprotective effect of palmatine against acetic acid-induced gastric ulcers in rats - Ling Wang; Xue Wang; Su-Li Zhang; Xiao-Ming Zhu; Yan-Qi Liu; Zi-Jing Song; Wen-Juan Du; Jun Ji; Cheng-Long Cui; Xin He; Chun-Feng Zhang; Chang-Run Guo; et al. (Journal of Natural Medicines, 2017)

Incentive effect of bentonite and concrete admixtures on stabilization/solidification for heavy metal-polluted sediments of Xiangjiang River - Ming Yan; Guangming Zeng; Xiaoming Li; Jianmin He; Guiqiu Chen; Danlian Huang; Lin Tang; Cui Lai; Chang Zhang; Xiaodong Li; Lichao Wang; Zhi Guo; et al. (Environmental Science and Pollution Research, 2017)

iTRAQ-Based Comparative Proteomics Analysis of the Fruiting Dikaryon and the Non-fruiting Monokaryon of Flammulina velutipes - Jing-Yu Liu; Ming-chang Chang; Jun-long Meng; Cui-ping Feng; Yong-nan Liu (Current Microbiology, 2017)

T cell infiltration is associated with kidney injury in patients with anti-glomerular basement membrane disease - Shui-Yi Hu; Xiao-Yu Jia; Jian-Nan Li; Xin Zheng; Jie Ao; Gang Liu; Zhao Cui; Ming-Hui Zhao (Science China Life Sciences, 2016)

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

Two new sesquiterpenes from Chloranthus japonicus Sieb - Qiang-Qiang Lu; Xin-Wei Shi; Shao-Jun Zheng; Jun-Hui Zhou; Xin-Ai Cui; Jin-Ming Gao (Natural Product Research, 2016)

NF-κB Blockade in Hypothalamic Paraventricular Nucleus Inhibits High-Salt-Induced Hypertension Through NLRP3 and Caspase-1 - Jie Qi; Xiao-Jing Yu; Xiao-Lian Shi; Hong-Li Gao; Qiu-Yue Yi; Hong Tan; Xiao-Yan Fan; Yan Zhang; Xin-Ai Song; Wei Cui; Jin-Jun Liu; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Comparison of the immunogenicity of two inactivated recombinant rabies viruses overexpressing the glycoprotein - Muhammad Tariq Navid; Yingying Li; Ming Zhou; Min Cui; Zhen F. Fu; Lijun Tang; Ling Zhao (Archives of Virology, 2016)

Present-Day Crustal Vertical Motion Around the Ordos Block Constrained by Precise Leveling and GPS Data - Ming Hao; Qingliang Wang; Duxin Cui; Liwei Liu; Lin Zhou (Surveys in Geophysics, 2016)

Combined treatment with parathyroid hormone (1–34) and beta-tricalcium phosphate had an additive effect on local bone formation in a rat defect model - Zhou-Shan Tao; Kai-kai Tu; Zheng-Liang Huang; Qiang Zhou; Tao Sun; Hong-Ming Xu; Yu-Long Zhou; Yang-Xun Lv; Wei Cui; Lei Yang (Medical & Biological Engineering & Computing, 2016)

Ecological species groups and interspecific association of vegetation in natural recovery process at Xiejiadian landslide after 2008 Wenchuan earthquake - Qing-wei Yang; Shou-jiang Liu; Cui-hua Hu; Ye-bin Lin; Bin Zhang; Ming-liang Luo; Hui-ling Peng (Journal of Mountain Science, 2016)

MLL2 is essential for porcine embryo development in vitro - Ming-Hui Zhao; Shuang Liang; Nam-Hyung Kim; Xiang-Shun Cui (In Vitro Cellular & Developmental Biology - Animal, 2016)

OsMSR15 encoding a rice C2H2-type zinc finger protein confers enhanced drought tolerance in transgenic Arabidopsis - Xin Zhang; Bin Zhang; Ming Juan Li; Xu Ming Yin; Li Fang Huang; Yan Chun Cui; Man Ling Wang; Xinjie Xia (Journal of Plant Biology, 2016)

Geophysical monitoring technology for CO2 sequestration - Jin-Feng Ma; Lin Li; Hao-Fan Wang; Ming-You Tan; Shi-Ling Cui; Yun-Yin Zhang; Zhi-Peng Qu; Ling-Yun Jia; Shu-Hai Zhang (Applied Geophysics, 2016)

Seismic dynamic monitoring in CO2 flooding based on characterization of frequency-dependent velocity factor - Jun-Hua Zhang; Jun Li; Wen Xiao; Ming-You Tan; Yun-Ying Zhang; Shi-Ling Cui; Zhi-Peng Qu (Applied Geophysics, 2016)

Dexmedetomidine Dose-Dependently Attenuates Ropivacaine-Induced Seizures and Negative Emotions Via Inhibiting Phosphorylation of Amygdala Extracellular Signal-Regulated Kinase in Mice - Ming-Zhu Zhai; Huang-Hui Wu; Jun-Bin Yin; Yuan-Yuan Cui; Xiao-Peng Mei; Han Zhang; Xia Zhu; Xue-Feng Shen; Alan David Kaye; Guo-Zhong Chen (Molecular Neurobiology, 2016)

GiT-based structural geologic feature analysis of the southern segment of Longmenshan fault zone for earthquake evidence - Cheng-ming Ye; Peng Cui; Saied Pirasteh; Jonathan Li; Qingkai Meng; Xiao-jia Bi; Jian-qiang Zhang (Journal of Mountain Science, 2016)

Factors Associated with Thrombolysis Outcome in Ischemic Stroke Patients with Atrial Fibrillation - Qiuyun Zhao; Xiaobo Li; Wanli Dong; Min Ye; Yongjun Cao; Meijuan Zhang; Qiantao Cheng; Junshan Zhou; Guofang Chen; Ming Yu; Shanshan Hong; Xiue Wei; et al. (Neuroscience Bulletin, 2016)

Silicon nutrition alleviates the lipid peroxidation and ion imbalance of Glycyrrhiza uralensis seedlings under salt stress - Yue-Tong Li; Wen-Jin Zhang; Jia-Jia Cui; Duo-Yong Lang; Ming Li; Qi-Peng Zhao; Xin-Hui Zhang (Acta Physiologiae Plantarum, 2016)

Active capping technology: a new environmental remediation of contaminated sediment - Chang Zhang; Meng-ying Zhu; Guang-ming Zeng; Zhi-gang Yu; Fang Cui; Zhong-zhu Yang; Liu-qing Shen (Environmental Science and Pollution Research, 2016)

Comprehensive analyses of the initiation and entrainment processes of the 2000 Yigong catastrophic landslide in Tibet, China - Jia-wen Zhou; Peng Cui; Ming-hui Hao (Landslides, 2016)

The c-Jun N-terminal kinase (JNK) is involved in H5N1 influenza A virus RNA and protein synthesis - Shouping Zhang; Haiyan Tian; Jingmin Cui; Jin Xiao; Ming Wang; Yanxin Hu (Archives of Virology, 2016)

Trend of water resource amount, drought frequency, and agricultural exposure to water stresses in the karst regions of South China - Long Wan; Jinxing Zhou; Hongyan Guo; Ming Cui; Yuguo Liu (Natural Hazards, 2016)

Contribution of Variants in CHRNA5/A3/B4 Gene Cluster on Chromosome 15 to Tobacco Smoking: From Genetic Association to Mechanism - Li Wen; Keran Jiang; Wenji Yuan; Wenyan Cui; Ming D. Li (Molecular Neurobiology, 2016)

FGF2 Prevents Sunitinib-Induced Cardiotoxicity in Zebrafish and Cardiomyoblast H9c2 Cells - Guozhen Cui; Huanxian Chen; Wei Cui; Xiaogang Guo; Jiansong Fang; Ailin Liu; Yonglong Chen; Simon Ming Yuen Lee (Cardiovascular Toxicology, 2016)

A Massively Parallel Computational Method of Reading Index Files for SOAPsnv - Xiaoqian Zhu; Shaoliang Peng; Shaojie Liu; Yingbo Cui; Xiang Gu; Ming Gao; Lin Fang; Xiaodong Fang (Interdisciplinary Sciences: Computational Life Sciences, 2015)

Synthesis and Application of Modified Zero-Valent Iron Nanoparticles for Removal of Hexavalent Chromium from Wastewater - Dan-Lian Huang; Guo-Min Chen; Guang-Ming Zeng; Piao Xu; Ming Yan; Cui Lai; Chen Zhang; Ning-Jie Li; Min Cheng; Xiao-Xiao He; Yan He (Water, Air, & Soil Pollution, 2015)

Slowly Digestible Starch—A Review - Ming Miao; Bo Jiang; Steve W. Cui; Tao Zhang; Zhengyu Jin (Critical Reviews in Food Science and Nutrition, 2015)

Sediment delivery across multiple spatio-temporal scales in an agriculture watershed of the Chinese Loess Plateau - Ming-guo Zheng; Run-kui Li; Ji-jun He; Ming Cui (Journal of Mountain Science, 2015)

Dynamic evolution of resistance gene analogs in the orthologous genomic regions of powdery mildew resistance gene MlIW170 in Triticum dicoccoides and Aegilops tauschii - Yong Liang; De-Yun Zhang; Shuhong Ouyang; Jingzhong Xie; Qiuhong Wu; Zhenzhong Wang; Yu Cui; Ping Lu; Dong Zhang; Zi-Ji Liu; Jie Zhu; Yong-Xing Chen; et al. (Theoretical and Applied Genetics, 2015)

Effects of tung oilseed FAD2 and DGAT2 genes on unsaturated fatty acid accumulation in Rhodotorula glutinis and Arabidopsis thaliana - Yicun Chen; Qinqin Cui; Yongjie Xu; Susu Yang; Ming Gao; Yangdong Wang (Molecular Genetics and Genomics, 2015)

Response of extracellular carboxylic and thiol ligands (oxalate, thiol compounds) to Pb2+ stress in Phanerochaete chrysosporium - Ningjie Li; Guangming Zeng; Danlian Huang; Chao Huang; Cui Lai; Zhen Wei; Piao Xu; Chen Zhang; Min Cheng; Ming Yan (Environmental Science and Pollution Research, 2015)

Isolation and characterization of thirty-eight microsatellite loci for the Pinus wangii, an endangered species - Zhi-Yong Zhang; Binbin Cui; Jian-Feng Mao; Xiao-Ming Pang; Ying-Yue Li (Conservation Genetics Resources, 2015)

Bacillus dabaoshanensis sp. nov., a Cr(VI)-tolerant bacterium isolated from heavy-metal-contaminated soil - Xiaowen Cui; Yueqiang Wang; Jing Liu; Ming Chang; Yong Zhao; Shungui Zhou; Li Zhuang (Archives of Microbiology, 2015)

Arenimonas taoyuanensis sp. nov., a novel bacterium isolated from rice-field soil in China - Shi-Ying Zhang; Wei Xiao; Yun-Sheng Xia; Yong-Xia Wang; Xiao-Long Cui; Nai-Ming Zhang (Antonie van Leeuwenhoek, 2015)

Novel polymorphic EST-derived microsatellite markers for the red-listed five needle pine, Pinus dabeshanensis - Zhi-Yong Zhang; Bin-Bin Cui; Jian-Feng Mao; Xiao-Ming Pang; Hui Liu; Ying-Yue Li (Conservation Genetics Resources, 2015)

Updated Findings of the Association and Functional Studies of DRD2/ANKK1 Variants with Addictions - Yunlong Ma; Wenji Yuan; Xianzhong Jiang; Wen-Yan Cui; Ming D. Li (Molecular Neurobiology, 2015)

Comparison of chemical, electrical, and combined activation methods for in vitro matured porcine oocytes - Shuai Liu; Kuiqing Cui; Hong Li Li; Jun Ming Sun; Xing Rong Lu; Kai Yuan Shen; Qing You Liu; De Shun Shi (In Vitro Cellular & Developmental Biology - Animal, 2015)

EGFR-AKT-mTOR activation mediates epiregulin-induced pleiotropic functions in cultured osteoblasts - Jian-bo Fan; Wei Liu; Xin-hui Zhu; Kun Yuan; Da-wei Xu; Jia-jia Chen; Zhi-ming Cui (Molecular and Cellular Biochemistry, 2015)

Application of molecularly imprinted polymers in wastewater treatment: a review - Dan-Lian Huang; Rong-Zhong Wang; Yun-Guo Liu; Guang-Ming Zeng; Cui Lai; Piao Xu; Bing-An Lu; Juan-Juan Xu; Cong Wang; Chao Huang (Environmental Science and Pollution Research, 2015)

The Effects of Wubeizi Ointment on the Proliferation of Keloid-Derived Fibroblasts - Ji-cun Ding; Zhi-ming Tang; Xiao-xiang Zhai; Xiang-hui Chen; Jing-guo Li; Cui-xia Zhang (Cell Biochemistry and Biophysics, 2015)
To evaluate the effectiveness of the Wubeizi (WBZ) ointment on keloid-derived fibroblasts. The primary cells of the keloid-derived fibroblasts were cultured and the effectiveness of the WBZ ointment at different concentrations was examined by MTT colorimetric methods on keloid-derived fibroblasts. The WBZ ointment showed inhibitory effects on proliferating the keloid-derived fibroblasts ( P < 0.01)in a time- and dose-dependent manner. The proportion of cells in S stage was significantly higher in each of the WBZ ointment group than in the control group ( P <0.01), and the proportion of G 2 + M stage cells was significantly lower than that of control group, which was statistically significant ( P < 0.01).The inhibitory effects of the S and G 2 + M stage increased with higher drug concentrations ( P < 0.05). Conclusion: The WBZ ointment can inhibit the proliferation of the keloid-derived fibroblasts in a time- and dose- dependent manner.

Genome-Wide Analysis of the C3H Zinc Finger Transcription Factor Family and Drought Responses of Members in Aegilops tauschii - An-Long Jiang; Zhao-Shi Xu; Guang-Yao Zhao; Xiao-Yu Cui; Ming Chen; Lian-Cheng Li; You-Zhi Ma (Plant Molecular Biology Reporter, 2014)

Zinc depletion activates porcine metaphase II oocytes independently of the protein kinase C pathway - Ming-Hui Zhao; Nam-Hyung Kim; Xiang-Shun Cui (In Vitro Cellular & Developmental Biology - Animal, 2014)

Functional analysis of FABP3 in the milk fat synthesis signaling pathway of dairy cow mammary epithelial cells - Meng-yao Liang; Xiao-ming Hou; Bo Qu; Na Zhang; Nan Li; Ying-jun Cui; Qing-zhang Li; Xue-jun Gao (In Vitro Cellular & Developmental Biology - Animal, 2014)

Selenium Promotes the Growth and Photosynthesis of Tomato Seedlings Under Salt Stress by Enhancing Chloroplast Antioxidant Defense System - Ming Diao; Long Ma; Jianwei Wang; Jinxia Cui; Aifei Fu; Hui-ying Liu (Journal of Plant Growth Regulation, 2014)

Halomonas qiaohouensis sp. nov., isolated from salt mine soil in southwest China - Yong-Xia Wang; Wei Xiao; Ming-Hua Dong; Qin Zhao; Zhi-Ying Li; Yong-Hong Lai; Xiao-Long Cui (Antonie van Leeuwenhoek, 2014)

Effect of enrofloxacin and emodin on heat-shock proteins’ expression in hepatic cells of grass carp (Ctenopharyngodon idellus) - Yanting Cui; Bo Liu; Jun Xie; Pao Xu; Yuanyuan Zhang; Jianhua Ming (Aquaculture International, 2014)

Brassinosteroid-mediated regulation of agronomic traits in rice - Cui Zhang; Ming-yi Bai; Kang Chong (Plant Cell Reports, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Inhibition of 12/15 lipoxygenase by baicalein reduces myocardial ischemia/reperfusion injury via modulation of multiple signaling pathways - Lina Song; Hui Yang; Hong-Xia Wang; Cui Tian; Yu Liu; Xiang-Jun Zeng; Erhe Gao; Yu-Ming Kang; Jie Du; Hui-Hua Li (Apoptosis, 2014)

Expression of Nemo-like kinase after spinal cord injury in rats - Dawei Xu; Wei Zhao; Gang Pan; Ming Qian; Xinhui Zhu; Wei Liu; Gang Cai; Zhiming Cui (Journal of Molecular Neuroscience, 2014)

The Novel Tetramethylpyrazine Bis-nitrone (TN-2) Protects Against MPTP/MPP+-Induced Neurotoxicity via Inhibition of Mitochondrial-Dependent Apoptosis - Daping Xu; Hongwei Duan; Zaijun Zhang; Wei Cui; Liang Wang; Yewei Sun; Ming Lang; Pui Man Hoi; Yifan Han; Yuqiang Wang; Simon MingYuen Lee (Journal of Neuroimmune Pharmacology, 2014)

Degradation of the potential rodent contraceptive quinestrol and elimination of its estrogenic activity in soil and water - Quan Zhang; Cui Wang; Wanpeng Liu; Jiapeng Qu; Ming Liu; Yanming Zhang; Meirong Zhao (Environmental Science and Pollution Research, 2014)

Whole exome sequencing identifies mutation of EDNRA involved in ACTH-independent macronodular adrenal hyperplasia - Jie Zhu; Liang Cui; Wei Wang; Xing-Yi Hang; A-Xiang Xu; Su-Xia Yang; Jing-Tao Dou; Yi-Ming Mu; Xu Zhang; Jiang-Ping Gao (Familial Cancer, 2013)

Oldest zircon xenocryst (4.17 Ga) from the North China Craton - Pei-Long Cui; Jing-Gui Sun; De-Ming Sha; Xi-Jing Wang; Peng Zhang; A-Lei Gu; Zhong-Yu Wang (International Geology Review, 2013)

cDNA cloning and mRNA expression of retinoid-X-receptor in the ovary of the shrimp Metapenaeus ensis - Ju Cui; Longtao Wu; Siu-Ming Chan; Ka Hou Chu (Molecular Biology Reports, 2013)

Circulating microparticles in patients with coronary heart disease and its correlation with interleukin-6 and C-reactive protein - Ying Cui; Lihui Zheng; Ming Jiang; Ru Jia; Xiao Zhang; Qishan Quan; Guiqin Du; Dongjin Shen; Xiaodan Zhao; Wenying Sun; Hongwei Xu; Lijuan Huang (Molecular Biology Reports, 2013)

Structure and dynamics of the bacterial communities in fermentation of the traditional Chinese post-fermented pu-erh tea revealed by 16S rRNA gene clone library - Ming Zhao; Wei Xiao; Yan Ma; Tingting Sun; Wenxia Yuan; Na Tang; Donglian Zhang; Yongxia Wang; Yali Li; Hongjie Zhou; Xiaolong Cui (World Journal of Microbiology and Biotechnology, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Cambium reactivation independent of bud unfolding involves de novo IAA biosynthesis in cambium regions in Populus tomentosa Carr. - Wan-Feng Li; Qi Ding; Ke-Ming Cui; Xin-Qiang He (Acta Physiologiae Plantarum, 2013)

A mutation in a coproporphyrinogen III oxidase gene confers growth inhibition, enhanced powdery mildew resistance and powdery mildew-induced cell death in Arabidopsis - Chuan-yu Guo; Guang-heng Wu; Jin Xing; Wen-qi Li; Ding-zhong Tang; Bai-ming Cui (Plant Cell Reports, 2013)

Expression of R132H Mutational IDH1 in Human U87 Glioblastoma Cells Affects the SREBP1a Pathway and Induces Cellular Proliferation - Jian Zhu; Gang Cui; Ming Chen; Qinian Xu; Xiuyun Wang; Dai Zhou; Shengxiang Lv; Linshan Fu; Zhong Wang; Jianling Zuo (Journal of Molecular Neuroscience, 2013)

Arbuscular mycorrhizal symbiosis and active ingredients of medicinal plants: current research status and prospectives - Yan Zeng; Lan-Ping Guo; Bao-Dong Chen; Zhi-Peng Hao; Ji-Yong Wang; Lu-Qi Huang; Guang Yang; Xiu-Ming Cui; Li Yang; Zhao-Xiang Wu; Mei-Lan Chen; Yan Zhang (Mycorrhiza, 2013)

The survey of porcine teschoviruses in field samples in China with a universal rapid probe real-time RT-PCR assay - Chaofan Zhang; Zhongtian Wang; Feng Hu; Yebing Liu; Zheng Qiu; Shun Zhou; Shangjin Cui; Ming Wang (Tropical Animal Health and Production, 2013)

Characteristics, causes and mitigation of catastrophic debris flow hazard on 21 July 2011 at the Longda Watershed of Songpan County, China - Yong-gang Ge; Peng Cui; Xiao-jun Guo; Guo-hu Song; Wei-ming Liu (Journal of Mountain Science, 2013)

Quantitative assessment and spatial characteristic analysis of agricultural drought risk in China - Bin He; Jianjun Wu; Aifeng Lü; Xuefeng Cui; Lei Zhou; Ming Liu; Lin Zhao (Natural Hazards, 2013)

Engineering properties of GMZ bentonite-sand as buffer/backfilling material for high-level waste disposal - Ming Zhang; Huyuan Zhang; Suli Cui; Lingyan Jia; Lang Zhou; Hang Chen (European Journal of Environmental and Civil Engineering, 2012)

Limonoids from the leaves of Swietenia macrophylla - Jie-Qing Liu; Cui-Fang Wang; Jian-Chao Chen; Ming-Hua Qiu (Natural Product Research, 2012)

Rosiglitazone inhibits angiotensin II-induced C-reactive protein production in human aortic endothelial cells through regulating AT1–ROS–MAPK signal pathway - Chun-Jie Han; Jun-Tian Liu; Ming Li; Mu Cui; Xiao-Ming Pang; Jun-Jun Mao; Xiao-Fang Liu (Inflammation Research, 2012)

Functional Analysis of Cotton DELLA-Like Genes that are Differentially Regulated during Fiber Development - Wei Wen; Baiming Cui; Xiaoling Yu; Qiang Chen; Yinying Zheng; Yiji Xia; Ming Peng (Plant Molecular Biology Reporter, 2012)

Genetics of GABAergic signaling in nicotine and alcohol dependence - Wen-Yan Cui; Chamindi Seneviratne; Jun Gu; Ming D. Li (Human Genetics, 2012)

Large-scale genome-wide association study of Asian population reveals genetic factors in FRMD4A and other loci influencing smoking initiation and nicotine dependence - Dankyu Yoon; Young-Jin Kim; Wen-Yan Cui; Andrew Van der Vaart; Yoon Shin Cho; Jong-Young Lee; Jennie Z. Ma; Thomas J. Payne; Ming D. Li; Taesung Park (Human Genetics, 2012)

An antifungal compound from Trichoderma harzianum SQR-T037 effectively controls Fusarium wilt of cucumber in continuously cropped soil - Li-Hua Chen; Ya-Qing Cui; Xing-Ming Yang; Di-Kun Zhao; Qi-Rong Shen (Australasian Plant Pathology, 2012)

TNF-α Increases Bone Marrow Mesenchymal Stem Cell Migration to Ischemic Tissues - Qiong Xiao; Shi-kun Wang; Hua Tian; Li Xin; Zhi-geng Zou; Yan-lai Hu; Cui-ming Chang; Xue-ying Wang; Qun-sheng Yin; Xiang-hong Zhang; Li-yan Wang (Cell Biochemistry and Biophysics, 2012)

Isolation and Identification of Endophytic Fungi in Roots of Nine Holcoglossum Plants (Orchidaceae) Collected from Yunnan, Guangxi, and Hainan Provinces of China - Xiao-Ming Tan; Xiao-Mei Chen; Chun-Lan Wang; Xiao-Hua Jin; Jin-Long Cui; Juan Chen; Shun-Xing Guo; Li-Fang Zhao (Current Microbiology, 2012)

A Promising CdSe@CdS-Quantum Dots-Cysteine for the Determination of Trace IgE by Solid Substrate Room Temperature Phosphorescence Immunoassay - Jia-Ming Liu; Li-ping Lin; Zhen-Bo Liu; Min-Lan Yang; Xin-xing Wang; Li-hong Zhang; Ma-lin Cui; Li Jiao (Journal of Fluorescence, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Thyroid disruption effects of environmental level perfluorooctane sulfonates (PFOS) in Xenopus laevis - Yan Cheng; Yuan Cui; Hui-ming Chen; Wen-ping Xie (Ecotoxicology, 2011)

Enhancing phosphorus availability in phosphorus-fertilized zones by reducing phosphate adsorbed on ferrihydrite using rice straw-derived biochar - Hao-Jie Cui; Ming Kuang Wang; Ming-Lai Fu; En Ci (Journal of Soils and Sediments, 2011)

Predominance of Precipitation and Temperature Controls on Ecosystem CO2 Exchange in Zoige Alpine Wetlands of Southwest China - Yan Bin Hao; Xiao Yong Cui; Yan Fen Wang; Xu Rong Mei; Xiao Ming Kang; Ning Wu; Peng Luo; Dan Zhu (Wetlands, 2011)

Evolution of kaolinite subgroup minerals and mixed-layer illite/smectite in the Paleogene Damintun Depression in Liaohe Basin of China and its implication for paleotemperature - Ming Zhao; JunFeng Ji; ZhenYan Chen; XiaoMing Chen; XiangDong Cui; YanShan Wang (Science China Earth Sciences, 2011)

Aging promotes todorokite formation from layered manganese oxide at near-surface conditions - Haojie Cui; Fan Liu; Xionghan Feng; Wenfeng Tan; Ming Kuang Wang (Journal of Soils and Sediments, 2010)

Erratum to: Nicotinic Modulation of Innate Immune Pathways Via α7 Nicotinic Acetylcholine Receptor - Wen-Yan Cui; Ming D. Li (Journal of Neuroimmune Pharmacology, 2010)

Nicotinic Modulation of Innate Immune Pathways Via α7 Nicotinic Acetylcholine Receptor - Wen-Yan Cui; Ming D. Li (Journal of Neuroimmune Pharmacology, 2010)

Estimation of water dynamics in a vertical-flow constructed wetland with a growing plant species - Ying Ouyang; Shi Ming Luo; Li Hua Cui; Ying Hu Liu; Zhong Qin (Journal of Soils and Sediments, 2010)

Modification of cambial cell wall architecture during cambium periodicity in Populus tomentosa Carr. - Hui-Min Chen; Jia-Jia Han; Ke-Ming Cui; Xin-Qiang He (Trees, 2010)

Replication and extension of association of choline acetyltransferase with nicotine dependence in European and African American smokers - Jinxue Wei; Jennie Z. Ma; Thomas J. Payne; Wenyan Cui; Riju Ray; Nandita Mitra; Caryn Lerman; Ming D. Li (Human Genetics, 2010)

Characteristics and sources of atmospheric polycyclic aromatic hydrocarbons (PAHs) in Shanghai, China - Xian Yu Wang; Qing Bo Li; Yong Ming Luo; Qian Ding; Lian Min Xi; Jian Min Ma; Yan Li; Yi Peng Liu; Cui Li Cheng (Environmental Monitoring and Assessment, 2010)

Sanchi ginseng (Panax notoginseng (Burkill) F. H. Chen) in China: distribution, cultivation and variations - Hong Bo Guo; Xiu Ming Cui; Na An; Ge Ping Cai (Genetic Resources and Crop Evolution, 2010)

Mechanism of the Formation for Thoracic Impedance Change - Ming-Xing Kuang; Qiu-Jin Xiao; Chao-Ying Cui; Nan-Zhen Kuang; Wen-Qin Hong; Ai-Rong Hu (Annals of Biomedical Engineering, 2010)

Tourist behaviors in wetland park: A preliminary study in Xixi National Wetland Park, Hangzhou, China - Lili Pan; Lijuan Cui; Ming Wu (Chinese Geographical Science, 2010)

Increased serum interleukin 17 in patients with systemic lupus erythematosus - Xue-Fei Zhao; Hai-Feng Pan; Hui Yuan; Wen-Hui Zhang; Xiang-Pei Li; Gui-Hong Wang; Guo-Cui Wu; Hong Su; Fa-Ming Pan; Wen-Xian Li; Lian-Hong Li; Guo-Ping Chen; et al. (Molecular Biology Reports, 2010)

Road landslide information management and forecasting system base on GIS - Wei Dong Wang; Xiang Gang Du; Cui Ming Xie (Environmental Monitoring and Assessment, 2009)

Des-γ-carboxy prothrombin stimulates human vascular endothelial cell growth and migration - Su-Bo Wang; Yan-Na Cheng; Shu-Xiang Cui; Julia Li Zhong; S. G. Ward; Li-Rui Sun; Ming-Hui Chen; Norihiro Kokudo; Wei Tang; Xian-Jun Qu (Clinical & Experimental Metastasis, 2009)

Remote sensing monitoring of tobacco field based on phenological characteristics and time series image—A case study of Chengjiang County, Yunnan Province, China - Guangxiong Peng; Lei Deng; Weihong Cui; Tao Ming; Wei Shen (Chinese Geographical Science, 2009)

The block of intracellular calcium release affects the pollen tube development of Picea wilsonii by changing the deposition of cell wall components - Kun-Ming Chen; Guo-Li Wu; Yu-Hua Wang; Cui-Ting Tian; Jozef Šamaj; František Baluška; Jin-Xing Lin (Protoplasma, 2008)

A novel derivative of xanomeline improved memory function in aged mice - Yi-Hui Cui; Wen Si; Liang Yin; Shu-Ming An; Jing Jin; Shi-Ning Deng; Xiao-Hua Cao (Neuroscience Bulletin, 2008)

A novel fibrinolytic enzyme from Cordyceps militaris, a Chinese traditional medicinal mushroom - Li Cui; Ming Sheng Dong; Xiao Hong Chen; Mei Jiang; Xin Lv; Guijun Yan (World Journal of Microbiology and Biotechnology, 2008)

Total deformation and its role in heavy precipitation events associated with deformation-dominant flow patterns - Shouting Gao; Shuai Yang; Ming Xue; Chunguang Cui (Advances in Atmospheric Sciences, 2008)

Formation of archegonium chamber is associated with nucellar-cell programmed cell death in Ginkgo biloba - Da-Hui Li; Xiong Yang; Ke-Ming Cui (Protoplasma, 2007)

Molecular Coordinated Regulation of Gene Expression During Ovarian Development in the Penaeid Shrimp - Ting Sze Lo; Zhaoxia Cui; Janice L.Y. Mong; Queenie W.L. Wong; Siu-Ming Chan; Hoi Shan Kwan; Ka Hou Chu (Marine Biotechnology, 2007)

Gene Cloning, Expression, and Substrate Specificity of an Imidase from the Strain Pseudomonas putida YZ-26 - Ya-wei Shi; Li-fang Cui; Jing-ming Yuan (Current Microbiology, 2007)

Soil erosion along a long slope in the gentle hilly areas of black soil region in Northeast China - Ming Cui; Qiangguo Cai; Axing Zhu; Haoming Fan (Journal of Geographical Sciences, 2007)

Quantification of the Impact of Land-Use Changes on Ecosystem Services: A Case Study in Pingbian County, China - Ren-Qiang Li; Ming Dong; Jian-Yong Cui; Li -Li Zhang; Qing-Guo Cui; Wei-Ming He (Environmental Monitoring and Assessment, 2007)

Solid Substrate-Room Temperature Phosphorescence Method for the Determination of Trace Mn(II) Based on Oxidizing Reaction of Hydrogen Peroxide Using α,α′-Bipyridine as Sensitizer - Jia-Ming Liu; Xiao-Jie Cui; Fei Gao; Lai-Ming Li; Xiu-Chai Huang; Min-Lan Yang; Fei-Ming Li; Hong Wu (Journal of Fluorescence, 2006)

Characterization of a novel impurity in bulk drug of lisinopril by multidimensional NMR technique - Dan-hua Wang; Sai-feng Pei; Ming-hua Zhou; Cui-rong Sun; Yuan-jiang Pan (Journal of Zhejiang University-SCIENCE B, 2006)

Experimental investigation of external explosion in the venting process - Zhi-min Du; Xin-qiao Jin; Dong-ming Cui; Jing-fang Ye (Journal of Zhejiang University-SCIENCE B, 2005)

Embryogenesis and Regeneration of Green Plantlets from Wheat (Triticum aestivum) Leaf Base - Cui-Ting Wang; Zhi-Ming Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

RAPD and SCAR markers linked to sex determination in Eucommia ulmoides Oliv. - Wen-Jie Xu; Bing-Wu Wang; Ke-Ming Cui (Euphytica, 2004)

The Nerve Supply to the Orbit of the Bactrian Camel - Sheng Cui; Jianlin Wang; Zheng Ming Xie (Veterinary Research Communications, 2004)

The Nervous Supply to the Nasal Cavity of the Bactrian Camel (Camelus Bactrianus) - Sheng Cui; Jian Hong Wang; Zheng Ming Xie (Veterinary Research Communications, 2004)

The petrology of a complex sodic and sodic?calcic amphibole association and its implications for the metasomatic processes in the jadeitite area in northwestern Myanmar, formerly Burma - Guang-Hai Shi; Wen-Yuan Cui; Peter Tropper; Chang-Qiu Wang; Gui-Ming Shu; Haixa Yu (Contributions to Mineralogy and Petrology, 2003)

Agronomic and morphological characterization of Agrobacterium-transformed Bt rice plants - Qing-yao Shu; Hai-rui Cui; Gong-yin Ye; Dian-xing Wu; Ying-wu Xia; Ming-wei Gao; Illimar Altosaar (Euphytica, 2002)

The gross anatomy of the cranial cervical ganglion and its branches in the bactrian camel (Camelus bactrianus) - Cui Sheng; Wang Jian-Ling; Xie Zhen-Ming (Veterinary Research Communications, 1998)